Polygonatum cyrtonema polysaccharide-based emulsion coating for postharvest preservation of satsuma mandarin and the underlying dual omics mechanisms - Yan Shi; Chenyu Wang; Lei Huo; Yihan Wang; Pan Wang; Miaomiao Yao; Jinping Si; Huqing Yang; Wanying Ge (Postharvest Biology and Technology, 2027)

DEM analysis of shear mechanical characteristics for rock fractures with a same roughness index θ* max /(C + 1) - Jiuyang Huan; Mingming He; Hengfei Pan; Weijia Yu; Chen Ge; Weitao Huan; Mengdie Hu (European Journal of Environmental and Civil Engineering, 2026)

Wastewater nutrients valorization into biostimulant via engineered polyphosphate-accumulating bacterium - Xiaotong Ge; Xue Li; Zihao Fan; Xin Wang; Mengmeng Wang; Jingyun Yin; Xiaohua Song; Liyu Pan; Yuhu Zheng; Liuyan Yang (Bioresource Technology, 2026)

From nonlinear neuronal dynamics to AI-optimized VLSI hardware: multiplier-free FPGA implementation of memristive FN-HR coupled neural networks for intelligent systems - Wei Wu; Wensen Yu; Chaochao Wang; Mohammad Sh. Daoud; Abdulilah Mohammad Mayet; Yisu Ge; Xiaotian Pan; Guodao Zhang (Cognitive Neurodynamics, 2026)

Root accumulation and efficient translocation of steroids in mangrove plants: Implications for an overlooked coastal reservoir - Ji-Xun Chen; Nian-Nian Wu; Shan Liu; Yuan Liu; Qin-Ge Zhou; Qing-Song Yang; Juan Ling; Xiao-Fang Huang; Yan-Kuan Tian; Chang-Gui Pan; Xiang-Rong Xu (Marine Pollution Bulletin, 2026)

Modified β-glucans promote saponin and fucosylated chondroitin sulfate biosynthesis in sea cucumber Apostichopus japonicus in association with activation of the TLR-MAPK signaling pathway - Zezheng Qi; Zeyu Zhang; Wenyue Dai; Hongmei Ma; Junpeng Ge; Yutong Yu; Mengling Cheng; Wenjian Zhao; Shihui Pan; Min Gu; Nan Bai (Fish & Shellfish Immunology, 2026)

Disruption of progesterone synthesis by PBDEs: Potent inhibition of human and rat placental 3β-hydroxysteroid dehydrogenase by the metabolite 4-Bromodiphenyl ether - Lubin Xie; Qianjin Fei; Ming Su; Yunbing Tang; Yang Zhu; Ren-shan Ge; Ping Duan; Chengshuang Pan (Toxicology and Applied Pharmacology, 2026)

Structure-activity relationship of per- and Polyfluoroalkyl substances as inhibitors of human and rat 17β-Hydroxysteroid dehydrogenase 3 - Chengshuang Pan; Jingjing Li; Fuhong Tian; Chentao Ding; Shaowei Wang; Ren-shan Ge; Qianjin Fei; Yang Zhu (Toxicology and Applied Pharmacology, 2026)

Late Cenozoic differential exhumation and tectonic transition of the Anninghe fault, southeastern Tibetan Plateau - Xichen Yao; Xiaoming Shen; Zhiyuan He; Xiaoping Yuan; Xuwen Shen; Yukui Ge; Shiguang Wang; Xueling Wang; Xuemin Pan; Yanglin Zhao (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Dual role of cold plasma in suppressing the growth, remodeling cellular ultrastructure and stimulating metabolic response of Kazachstania exigua from transcriptomic insight - Binyao Wang; Qing Du; Liangpeng Yuan; Longhua Pan; Yi Tang; Menglu Yang; Wenjian Wang; Dengshui Peng; Huajia Li; Shan Zeng; Lihong Ge; Jianping Yang; et al. (Food Research International, 2026)

Endogenously water-driven self-powered bioelectrical engineering scaffold mediates peripheral nerve regeneration - Guanhong Liu; Yazhou Lin; Haocheng Yang; Chengbai Dai; Rongze Tang; Kezhen Ge; Feng Yuan; Fenglei Gao; Bin Pan; Minghao Chao (Chemical Engineering Journal, 2026)

In situ real-time continuous monitoring of soil carbonate ions using a portable CuO–Cu2O-based electrochemical sensor - Yuying Bao; Jingfang Ji; Jiyu Chen; Kaiquan Li; Pan Liu; Jingmin Ge; Ronghan Wei; Xiaodong Lei; Jingwei Zhang (Analytica Chimica Acta, 2026)

Hydrological controls dominate greenhouse gas emissions in aquatic–terrestrial ecotones under extreme weather - Jingyun Yin; Wenbin Bian; Ke Xu; Liyu Pan; Di He; Chenyu Wang; Xiaohua Song; Xiaotong Ge; Chenyuan Kong; Yuhu Zheng; Hongqiang Ren; Mengmeng Wang; et al. (Journal of Environmental Sciences, 2026)

Optimization design and process intensification of hydrolysis distillation process for toluene diisocyanate tar residue - Dandan Li; Yuxuan Zhang; Shi Zhao; Jijun Ge; Guoxuan Li; Rongshan Bi; Pan Xu (Process Safety and Environmental Protection, 2026)

An efficient three-dimensional ocean wave reconstruction method based on adaptive strip-wise stereo matching - Hongfei Yao; Haojie Ren; Hao Ren; Lianxiang Chen; Yue Pan; Jinbo Chen; Hongbo Zhu; Haiyang Ge; Mingqiang Xu (Ocean Engineering, 2026)

Urinary biomarkers of emerging contaminants in relation to prevalent Parkinson's disease: An exploratory mixture and network toxicology study - Chiqun Shan; Yiming Ge; Junye Bian; Yuli Lin; Bo Fu; Qinru Xiao; Aihua Guo; Mengyan Li; Pan Xu; Yi Chen; Haobo Chen; Shaoyou Lu (Journal of Hazardous Materials, 2026)

ENSO impacts the scales of cyanobacterial bloom in Lake Taihu, China - Liyu Pan; Lian Xue; Mengmeng Wang; Di He; Xiaohua Song; Jingyun Yin; Xiaotong Ge; Guangwei Zhu; Bensheng You; Qing Cao; Hao Lu; Liuyan Yang (Journal of Environmental Management, 2026)

Green synthesis of N-doped hierarchical porous biochar from Artemisia leaf for enhanced peroxydisulfate activation: Synergistic roles of edge nitrogen and carbonyl group - Lin Ge; Zhan Chen; Yuan Pan; Xiansheng Zhang; Teng Li; Xinyi Huang; Binbin Shao; Sheng Liu; Yunze Wang; Yu Zhang; Zhifeng Liu (Environmental Research, 2026)

Effects of starch degradation and starch-lipid complexes recombination on starch digestion under cold plasma regulation - Yuan Jiang; Xingrong Pan; Yuanfang Sun; Jingru He; Sihan Cheng; Zonnglin Guo; Kun Hu; Xiangzhen Ge (Carbohydrate Polymers, 2026)

The Diversity of Lowland Representatives of the Highest‐Altitude Mammals: The Elusive Pikas of the Subgenus Alienauroa - Andrey A. Lissovsky; Xuan Pan; Georgy Shakula; Xuelong Jiang; Liang Lu; Shaoying Liu; Deyan Ge (Zoologica Scripta, 2026)
The pikas of the subgenus Alienauroa were discovered merely 25 years ago, with the principal diversity of this group described only in 2017. This study integrates genomic, morphological, and distributional data from all specimens collected to date to advance the understanding of phylogeny, taxonomy, and distribution within these pika species. Our analyses delineate four distinct species: O. syrinx , O. sacraria , O. huanglongensis, and O. flatcalvariam . The entire group is restricted to a limited geographic area situated between the Huanghe and Yangtze rivers. All species exhibit strict ecological association with dark coniferous forests. Two sister species, O. syrinx and O. sacraria , display disjunct distributions and significant genetic divergence, indicative of relict range fragmentation. In contrast, the second sister pair, O. huanglongensis and O. flatcalvariam , exhibit restricted distributions and lower levels of genetic variation. The species generally demonstrate allopatric distribution, with the exception of O. syrinx and O. sacraria in the Qinling and Dabashan mountains, where they exhibit sympatry.

Evaluation of Elaeagnus angustifolia extract in promoting osteogenesis of adipose-derived mesenchymal stem cells through modulation of intracellular signaling pathways - Bingxuan Wang; Zhiyou Zhou; Peijun Dai; Yubo Pan; Junyong Ge (Tissue and Cell, 2026)

Governing role of pore structure in solute transport processes in plain river network areas: Insights from CT imaging - Sun Xiaoqin; She Dongli; Pan Yongchun; Wang Hongde; Cao Taohong; Ge Jiamin; Ju Xinni (Soil and Tillage Research, 2026)

Divergent drivers of winter PM2.5 pollution in representative cities of the Sichuan Basin: Insights from observation and machine learning - Zhihan Rao; Hongli Tao; Li Zhou; Weigang Wang; Song Liu; Bin Luo; Wei Zhang; Pan Cao; Jianjun Li; Fumo Yang; Maofa Ge (Journal of Hazardous Materials, 2026)

Metal-phenolic microcapsules-reinforced hydrogel-based in situ tumor vaccine for postoperative adjuvant therapy - Xin Tan; Renwang Sheng; Yanling Liang; Yinghua Tao; Weikun Li; Nuoya Chen; Diyi Feng; Xinyang Pan; Shuangshuang Ma; Fangzhou Liu; Ling Liu; Liqin Ge (Chemical Engineering Journal, 2026)

PM2.5 exposure exacerbates cerebral infarction via HPG axis downregulation and pituitary lipid metabolism dysregulation in mice - Xin lv; Guanhui Pei; Lijuan Liu; Zhou zhou; Yicong Zhou; Binbin Wang; Chaoyue Meng; Ruomeng Chen; Qiang Yao; Ge Bai; Xuelin Wang; Minghan Zhao; et al. (NeuroToxicology, 2026)

Experimental study on combustion characteristics in a low-pressure direct-injection hydrogen engine - Tong Ge; Jinguang Li; Minghao Zhu; Fulai Zhao; Zhancheng Dou; Haiqiao Wei; Jiaying Pan (Fuel, 2026)

Carbon material–driven multistep electron transfer for efficient degradation of electron-rich pollutants: Synergistic effect of free radical and nonradical mechanisms - Meiyun Feng; Jiqiang Jia; Wenming Pei; Lichao Tan; Fukai Tang; Baoliu Pan; Keke Xu; Xin Liu; Mingzhu Zhang; Meng Zhang; Feng Ge (Chemical Engineering Journal, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Engineering Mn-confined Fe0-carbon with isolated oxygen-containing groups breaks the bottleneck for concurrent self-driven Fenton degradation of antibiotics and heavy metals immobilization - Yujiang Huang; Dan Liu; Zhouyang Shi; Tong Hu; Huiwang Dai; Sicheng Pan; Wenjun Zhou; Fei Ge; Daohui Lin; Lizhong Zhu (Journal of Hazardous Materials, 2026)

An interlayer-engineered faradaic electrosorption system for co-removal of amikacin and heavy metal ions: Fe/Mo dual activation, energy storage, and adsorption selectivity - Pan Gong; Changhai Ji; Chang Liu; Xiaoshuang Yin; Wenzhong Yang; Lin Zhang; Shaojun Jiao; Feng Ge; Kegui Zhang (Chemical Engineering Journal, 2026)

From selection to design: Reshaping aptamer discovery with artificial intelligence - Xin Yang; Shijian Ding; Meishen Ren; Huarui Zhang; Xiaohui Tao; Ning Zhang; Yihao Zhang; Hewen Jiange; Yufei Pan; Shanshan Yao; Luyao Wang; Yuan Ma; et al. (Chemical Engineering Journal, 2026)

Depolymerization mechanism of polybutylene succinate in subcritical water: Visual phase change and product distribution - Bo Xiao; Mian Hu; Jia-Yi Dong; Ya-Ge Zhang; Zhi-Gang Shen; Yi Liu; Jie-Xin Wang; Ziyan Pan; Zhong-Ting Hu (Chemical Engineering Journal, 2026)

Sandwich-structured porous foam from sodium alginate-intercalated MXene/polyethylene glycol: Photothermal conversion, phase change storage and electromagnetic interference shielding - Chengzhe Niu; Mingyu Li; Gaofei Pan; Jingwen Lu; Huitao Yu; Xin Ge; Wei Feng (Carbohydrate Polymers, 2026)

Hydrophobicity, 3D complexity, and steric feature affect salicylate inhibition of human and rat gonadal 3β-hydroxysteroid dehydrogenases: Insights from experiments to 3D-QSAR and in silico docking analysis - Xiya Ren; Zhuoqi Chen; Chengshuang Pan; Yingfen Ying; Yang Zhu; Ren-shan Ge; Yi Liu (Chemico-Biological Interactions, 2026)

Arbuscular mycorrhizal fungi hypha shape atrazine degradation ability of microbiota by increasing soil aggregation - Yang Sun; Hongyang Pan; Ge Song; Sisi Chen; Alexander V. Kurakov; Fuqiang Song; Jing Wang; Xiaoxu Fan (Mycorrhiza, 2026)

Atmospheric Boundary Layer Eco-Environment Shanghuang Observatory: An Integrated Multiscale Research Platform in Southeastern China for Understanding Boundary Layer Processes, Atmospheric Chemistry Feedback, and Extreme Weather–Climate Linkages - Zifa Wang; Xiaole Pan; Yele Sun; Jinyuan Xin; Hang Su; Junji Cao; Jie Li; Ting Yang; Hang Liu; Weijie Yao; Weiqi Xu; Xueshun Chen; et al. (Advances in Atmospheric Sciences, 2026)

A Galactose-Modified Light-Activatable Persulfurated Arene Fluorescent Probe for Targeted Imaging of Polarity and Viscosity in Liver Cancer Cells - Pan-Xin Ge; Yan Rong; Lu-Lu Sun; Yuqing Hu; Xianzhi Chai; Hai-Hao Han; Liangliang Zhu (Journal of Fluorescence, 2026)

Advances and Perspectives in Atmospheric Environment Modeling in China - Zifa Wang; Xinwei Li; Meng Gao; Baozhu Ge; Xiao Tang; Xueshun Chen; Qizhong Wu; Lin Wu; Zhe Wang; Ting Yang; Xiaole Pan; Huansheng Chen; et al. (Advances in Atmospheric Sciences, 2026)

l-Lysine effects on myosin carbonylation in metal-catalyzed oxidation: Implications for thermal gelation - Yuling Liu; Yuqi Wu; Ge Han; Jiaxin He; Yawen Wang; Jinfeng Pan; Shengjie Li (Food Research International, 2026)

Enhancing fruity aroma with exogenous tannins in red wines: A study on Marselan and Cabernet Sauvignon - Yilin Ge; Nongyu Xia; Hualin Zhang; Huimin Zhang; Fei He; Weiming Yang; Changqing Duan; Qiuhong Pan (Food Chemistry, 2026)

Groundwater pollution risk in a large agricultural irrigation plain assessed using modified DRASTIC-LU model, pollution loading and hazard analysis - Jiaqi Li; Chunli Su; Weili Ge; Zhiyuan Gan; Md Enamul Huq; Junting Liu; Yinchun Su; Hongjie Pan (Environmental Geochemistry and Health, 2026)

3D Geometry Scanning and Structural Integrity Assessment to Advance Meniscus Allograft Transplantation - Shuchun Sun; Ge Pan; Jichao Zhao; William Michael Pullen; Jian Chen; Haiyang Ma; William C. Bridges; Dustin Mueller; Hai Yao; Shangping Wang (Annals of Biomedical Engineering, 2026)
Purpose Meniscal allograft transplantation can restore joint biomechanics and alleviate symptoms, but its clinical use is limited by the scarcity of size-matched, structurally intact grafts. Current two-dimensional sizing and subjective inspection in tissue banks fail to capture complex three-dimensional geometry and subtle surface defects, highlighting the need for an accurate, reliable, and practical solution for routine donor tissue evaluation. Methods We developed an integrated system combining optical 3D scanning with curvature-based analysis for 3D geometry capture and surface defect detection in meniscus allografts. System performance was validated in terms of scanner accuracy and tissue bank workflow feasibility. Results The system completes each scan within 2 versus ~ 60 min for micro-computed tomography (μCT). It demonstrated μCT-comparable accuracy (mean volume difference: 6.9%; surface deviation: 8.3%). Scanning through phosphate buffer saline (PBS)-immersed transparent bags yielded equivalent accuracy to scanning in air (mean volume difference: 7.2%; surface deviation: 12.5%). The workflow demonstrated high intra- and inter-operator reproducibility. Viability testing revealed PBS-preserved tissues maintained > 94% viability for 20 min, whereas air-exposed tissues dropped below 70% within 10 min. For defect assessment, curvature metrics reliably identified surface wear, longitudinal, and radial defects, with size measurements for wear and longitudinal tears showing equivalence (± 10% margin) to stereomicroscopy. Conclusion This portable system enables accurate and rapid 3D scanning under tissue banking conditions and quantitative surface defect detection. It supports improved graft shape matching and surface defect screening, offering a practical and scalable solution for tissue banks and clinical settings, potentially extendable to other fibrocartilaginous and osteochondral tissues.

Microbial Community Traits and Necromass Dynamics Shape Soil Carbon Accumulation - Wankun Pan; Sheng Tang; Wolfgang Wanek; Zhongkui Luo; Ji Chen; Yuanhe Yang; Tida Ge; Karina A. Marsden; Guopeng Liang; David R. Chadwick; Xinping Chen; Andrew S. Gregory; et al. (Global Change Biology, 2026)
Soil organic carbon (SOC) sequestration is vital for food security and climate mitigation. However, its long‐term response to fertilisation remains unclear. Using the 180‐year Broadbalk Experiment (the world's longest‐running fertilisation trial; Rothamsted, UK), combined with 14 C labelling and metagenomics, we identified fundamentally distinct mechanisms of SOC accumulation: a microbially mediated dual pathway under organic fertilisation versus a resource‐limited pathway under inorganic fertilisation. Sustained organic inputs matched inorganic fertilisers in maintaining crop yields while increasing total SOC by 160% (relative to a no‐fertilisation control), far exceeding the 26% gain under inorganic fertilisation. Mechanistically, the continuous supply of labile organic matter provided an energetic surplus, allowing copiotrophic microbial communities with high carbon use efficiency to reduce investment in energy‐intensive enzyme synthesis. This metabolic efficiency facilitated a dual‐pathway expansion, elevating dynamic particulate organic carbon (POC) from 1.4 to 7.5 g kg −1 , while microbial assimilation and necromass accumulation concurrently increased mineral‐associated organic carbon (MAOC) from 6.8 to 21.5 g kg −1 . Conversely, inorganic fertilisation induced an oligotrophic ‘mining’ strategy, in which microorganisms upregulated the degradation of complex organic matter under carbon‐limited conditions, restricting sustained SOC accumulation primarily to the MAOC pool. A global meta‐analysis of field experiments (0–120 years) corroborated these temporal trajectories across diverse soil types, showing that SOC under organic fertilisation increases in a time‐dependent manner, reaching a 77% gain after 80 years (three‐fold greater than under inorganic inputs). Overall, organic fertilisation enhances total SOC via POC and MAOC accumulation, whereas inorganic fertilisation mainly increases MAOC. Long‐term SOC persistence depends not only on carbon inputs, but also on microbial community traits and necromass dynamics, suggesting that aligning nutrient inputs with these biological mechanisms is critical for sustainable carbon sequestration.

La-mediated green rust for synergistic nitrogen–phosphorus removal and targeted N2 formation regulated by built-in electric field and spin state - Yibo Zhang; Jun Nan; Chen Liang; Zhencheng Ge; Han Deng; Yanhan Che; Yunhao Pan; Meng Li; Bohan Liu (Water Research, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Unraveling the synergy of wheat-based probiotic- fermented modified dietary Fibers, resistant starch, and gluten in constructing high-quality, low Glycemic index noodles - Ai-Mei Liao; Xiao-ge Liu; Qiao-Qiao Lai; Jia-qi Wang; Kiran Thakur; Long Pan; Yin-Chen Hou; Na Liu; Xian-ming Liu; Zhao-Jun Wei (Food Chemistry, 2026)

Three-terminal quantum dot LEDs with integrate-and-fire neuron for on-device encryption - Ge Zhou; Youjiang Pan; Hailong Hu; Tailiang Guo; Fushan Li (Chemical Engineering Journal, 2026)

Dilute-O2-flash-etching introduced eco-fabrication of high-plateau-capacity hard carbon for performance sodium-ion batteries - Haonan Zhang; Jianjun Zhao; Anuj Kumar; Xiujie Ge; Yanzhi Sun; Mohd Ubaidullah; Junqing Pan (Chemical Engineering Journal, 2026)

Enhancing electrochemical CO2 reduction with monoamino-functionalized cobalt tetraphenylporphyrin catalysts - Li-Yuan Zhao; Hui Wang; Hao Tan; Jie Chao; Zhi-Hang Lin; Ge-Chuan-Qi Pan; Xiao-Ji Wang; Qiang Sun (Fuel, 2026)

Effects of carbonization temperature on the synthesis and antibacterial properties of honeysuckle carbon dots: Application in extending pork shelf life - Leyi Li; Gege Su; Yiheng Deng; Xue Pan; Jiayin Hou; Wenhao Luo; Hua Zheng; Hongtao Lei; Xiangzhen Ge; Zonglin Guo (Food Packaging and Shelf Life, 2026)

Ecological effects and strategies of Spartina alterniflora Loisel. removal in China - Zhanbin Luo; Fu Chen; Xi-En Long; Jing Ma; Jiyou Wei; Yudi Guo; Yanfeng Zhu; Yongjun Yang; Xiaoping Ge; Yanyan Kang; Ming Zou; Lei Liu; et al. (Environmental Impact Assessment Review, 2026)

A fast powerful X-ray transient from possible tidal disruption of a white dwarf - Dongyue Li; Wenda Zhang; Jun Yang; Jin-Hong Chen; Weimin Yuan; Huaqing Cheng; Fan Xu; Xinwen Shu; Rong-Feng Shen; Ning Jiang; Jiazheng Zhu; Chang Zhou; et al. (Science Bulletin, 2026)

Alleviating heavy metal migration risks by adding biochar during sludge amelioration of forest soil: Evaluating differential loss across multiple media - Yuantong Yang; Yangli Zhang; Xiaojun Ge; Peiqi Pan; Wei Zhang; Jiamin Zhang; Chaohai Wei; Jianbo Liao (Journal of Hazardous Materials, 2026)

Dual-enzyme co-immobilized aluminum-based metal-organic frameworks with hierarchical structure: Efficient and stable dual-enzyme cascade catalyst - Xia Gao; Huibin Pan; Weitong Dang; Jinhang Guo; Chengfang Qiao; Qian Liu; Chunsheng Zhou; Hongguang Ge; Yaqiang Zhang (Journal of Environmental Chemical Engineering, 2026)

Efficient arc-assisted electrothermal regeneration and modification of activated carbon - Xin Nie; Xihao Wang; Xiaojun Ma; Dong Pan; Shiyuan Zheng; Guojia Ge (Journal of Environmental Chemical Engineering, 2026)

Co-fermentation of Hanseniaspora uvarum and Saccharomyces cerevisiae improves flavor in low-alcohol peach beverages - Haiyan Yu; Lei Shi; Chen Chen; Chang Ge; Xin Pan; Qian Chen; Huaixiang Tian (Food Research International, 2026)

Enhancing the quality of sea cucumber Apostichopus japonicus: Dietary protein-to-carbohydrate ratio promotes saponin biosynthesis via metabolic reprogramming and activation of mevalonate pathway - Zezheng Qi; Nan Bai; Yuxin He; Zeyu Zhang; Junpeng Ge; Wenjian Zhao; Shihui Pan; Min Gu (Food Chemistry, 2026)

Associations of paraben exposures measured by repeated urinary biomarkers with sperm DNA damage and apoptosis - Xiu-Ting Li; Yu Miao; Min Zhang; Jia-Yue Zeng; Peng-Hui Liu; Yang-Juan Li; A-Xue Liu; Jin-Qin Zhu; Ning Zhang; Long Ge; Han-Qin Ye; Pan-Pan Chen; et al. (Environmental Research, 2026)

Engineering a living therapeutic: calcium phosphate-mineralized phycocyanobilin-producing E. coli as a self-contained photodynamic system - Yifan Wei; Nana Pan; Jingjing Du; Chao Wang; Xin Chen; Jin-ao Li; Li Lu; Baosheng Ge; Fang Huang; Xiaojuan Wang (Bioresource Technology, 2026)

Insights into the uplift mechanism of Gongga Shan, Eastern Tibetan Plateau: From the perspective of geomorphic and exhumation characteristics - Xueling Wang; Xiaoming Shen; Zhiyuan He; Xiaoping Yuan; Paul R. Eizenhöfer; Yukui Ge; Xuemin Pan; Xiong Wu; Yingying Jia; Yanglin Zhao (Tectonophysics, 2026)

Aerosol-cloud layer detection algorithm of the DQ-1/ACDL - Feiyue Mao; Weiwei Xu; Zengxin Pan; Lin Zang; Ge Han; Linxin Dai; Xiuqing Hu; Weibiao Chen; Wei Gong (Remote Sensing of Environment, 2026)

Agronomic management and soil properties dominate the production of pulses in China - Yalin Liu; Qiong Liu; Yixuan Chen; Chunjie Li; Yakov Kuzyakov; Didier Lesueur; Christian Schöb; Huijie Zhang; Hongquan Liu; Xuejun Wang; Peng Pan; Zeyan Zhang; et al. (European Journal of Agronomy, 2026)

Fractional derivative viscoelastic models based on L2-1σ formula: modelling and numerical application - Pan Ding; Riqing Xu; Lixing Wang; Zhiran Gao; Xiaonan Ge; Minjie Wen (Computers and Geotechnics, 2026)

Synergistic catalysis over Fe Cu dual single-atom sites boosting direct oxidation of methane to C1 oxygenates - Weiqin Shen; Chuanhao Yao; Baiyang Yu; Shasha Ge; Xuan Tang; Jing Xu; Ying Zhang; Chengsi Pan; Yongfa Zhu; Yang Lou (Chemical Engineering Journal, 2026)

Facile synthesis of macroporous foams with unique bone-like structure for the encapsulation of polyethylene glycol by sodium alginate for thermal energy storage - Xin Ge; Hao Xiong; Chengzhe Niu; Mingyu Li; Huitao Yu; Lina Jia; Ruiguang Xing; Gaofei Pan; Yanan Li; Jinxiao Bao (Carbohydrate Polymers, 2026)

Groundwater denitrification dynamics and N2O emissions across diverse cultivated land types in the Taihu lake region - Taohong Cao; Dongli She; Yongchun Pan; Jiamin Ge; Shenhao Qu; Xinni Ju; Xuan Huang; Yongqiu Xia; Daniel Fernàndez-Garcia (Water Research, 2025)

Gut-protective effects of dietary niacin in juvenile turbot (Scophthalmus maximus L.) fed a high-lipid diet: modulation of mucosal immune response, barrier function, and gut microbiota - Xiaoyuan Ge; Jintao Pan; Junming Deng; Kangsen Mai; Yanjiao Zhang (Fish & Shellfish Immunology, 2025)

Enhancing vitrification of viable temporomandibular joint discs using DP6 solution - Dustin Mueller; Isabelle McDaniel; Marshall Wilson; Ge Pan; Haiyang Ma; Shangping Wang; Hai Yao (Cryobiology, 2025)

Radiofrequency electromagnetic heating enhanced vitrification of viable large cartilage tissues - Haiyang Ma; Josh Wewerk; Ge Pan; A.J. Riffe; Peng Chen; Yaqian Sun; John M. Alford; Kristi Helke; Girish Srinivas; Hai Yao; David P. Eisenberg; Shangping Wang (Cryobiology, 2025)

Four-month evaluation of vitrified meniscal allograft transplantation in a pig model - Ge Pan; Haiyang Ma; Kristi Helke; William Michael Pullen; Meenakshi Mukherji; Daniel Eldridge; Peng Chen; Dustin Mueller; Shuchun Sun; Yongren Wua; Tong Ye; Hai Yao; et al. (Cryobiology, 2025)

Structural characterization of polysaccharides from lactobacillus helveticus MB2–1 fermented milk and their interaction mechanisms with casein in modulating gel stability - Zhiwen Ge; Dan Wang; Fidelis Azi; Peiyou Qin; Wenting Zhao; Pan Wang; Xiaoyan Zhao; Ye Liu (Carbohydrate Polymers, 2025)

Provenance and geogenic modes of high-fluoride groundwater occurred in various sedimentary environments: constraints of hydrogeology and hydrogeochemstry - Guojie Feng; Zhiqin Li; Chunli Su; Xianjun Xie; Weili Ge; Yiqun Gan; Zhaohui Luo; Kunfu Pi; Hongjie Pan; Yanhui Gao; Yanmei Yang (Applied Geochemistry, 2025)

Metabolic syndrome and risk of dementia and cognitive decline: a systematic review and meta-analysis of prospective cohort studies from 6,753,197 participants - Qi Wang; Luyi Zhang; Ruiqi Xu; Kexin Meng; Lutong Pan; Xiaoyu Zhang; Long Ge; Dongshan Zhu (GeroScience, 2025)

VOC emissions characteristics and cooperative control by combustion adjustment and APCDs in supercritical coal-fired power plants - Penghui Ge; Jie Wu; Longchun Zhong; Wei-Ping Pan (Journal of Hazardous Materials, 2025)

Cross-modal 2D-3D feature matching: simultaneous local feature description and detection across images and point clouds - Wei Ma; Yucheng Huang; Shengjun Tang; Xianwei Zheng; Zhen Dong; Liang Ge; Jianping Pan; Qingquan Li; Bing Wang (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

MoO3-MoS2 with abundant oxygen vacancies for real-time seafood quality assessment - Guochen Qi; Shuwei Ren; Jingfang Ji; Hao Gao; Zhichuang Ma; Sufeng Fan; Pan Liu; Jingmin Ge (Chemical Engineering Journal, 2025)

Impact of mycotoxins on placental function: Focus on cyclopiazonic acid, deoxynivalenol, patulin, and zearalenone's metabolites - Huiqian Zhang; Xiuwei Shen; Jiayi He; Qingyuan Wang; Yunbing Tang; Peipei Pan; Ren-Shan Ge; Xiaoheng Li (Chemico-Biological Interactions, 2025)

Impact of sodium intake on blood pressure, mortality and major cardiovascular events: an umbrella review of systematic reviews and meta-analyses - Qiuyu Yang; Robin W. M. Vernooij; Hongfei Zhu; Gihad Nesrallah; Chunyang Bai; Qi Wang; Ying Li; Danni Xia; Małgorzata M. Bała; Sylwia Warzecha; Mingyao Sun; Ahmad Jayedi; et al. (Critical Reviews in Food Science and Nutrition, 2025)

Development of a multifunctional and biocompatible hydrogel for flexible implantable sensors - Kaiqi Zhang; Huibiao You; Yuxi Liu; Fulei Lin; Yanan Li; Lina Jia; Jinxiao Bao; Xin Ge; Gaofei Pan; Huitao Yu; Ruiguang Xing (Chemical Engineering Journal, 2025)

Red blood cell-mimetic hollow covalent organic framework with oxygen-replenishing and cavitation-amplified for enhanced sonodynamic therapy of periodontitis - Yang Zhou; Qiyuan Pan; Ruolin Wang; Yan Ge; Xiao Zhang; Yifan Guo; Rongyin Sun; Xianglong Liu; Sainan Liu; Min Liu; Jun Lin (Chemical Engineering Journal, 2025)

Multiscale adaptive fusion network for joint classification of hyperspectral and LiDAR data - Haizhu Pan; Weiwei Zhao; Haimiao Ge; Hui Yan; Cuiping Shi (International Journal of Remote Sensing, 2025)

Prediction of next-day 1-km canopy urban heat island by integrating a multi-block convolutional neural network with satellite- and ground-based observations - Shuang Ge; Wenfeng Zhan; Jiufeng Li; Long Li; Pan Dong; Xiang Li; Chenguang Wang; Chunli Wang; Yihan Gao (Sustainable Cities and Society, 2025)

Role of circular RNAs in formaldehyde-induced lung Injury: Insights into expression and regulatory pathways - Pan Ge; Xiang Zhang; Yan-qi Yang; Jia-ming Xie; Mo-qi Lv; Ying Sun; Ya-zhao Li; Yuan-yuan Geng; Jian Zhang; Dang-xia Zhou (Food and Chemical Toxicology, 2025)

Ultrasound activated Zn Ga layered double oxide as ROS antimicrobial-healing system boosts antimicrobial effect and infected bone regeneration - Shengtao Dong; Yusheng Yang; Jiezhong Deng; Yewei Jia; Pan Liu; Zhengrong Chen; Jinyue He; Wenxi Bai; Wei Wang; Qicheng Ge; Ce Dou; Zehua Zhang (Chemical Engineering Journal, 2025)

Modified conductive additives based on pine needle-derived biomass carbon for high-performance lithium-ion batteries - Hao Ge; Zhonghai Xiu; Longhui Xie; Ruicong Pan; Bei Huang; Xiaoman Cao; Zhijia Sun (Biomass and Bioenergy, 2025)

Neutron resonance integral analysis of 238U within resolved resonance region - Yufei Pan; Jimin Wang; Ruirui Xu; Xi Tao; Yue Zhang; Jie Ren; Yuan Tian; Zhigang Ge; Nengchuan Shu; Kang Xing; Xiaofei Wu (Annals of Nuclear Energy, 2025)

Fe and Mn biogeochemical cycling associated with basin-scale redox dynamics traced by DOM degradation in different alluvial aquifers - Jiaqi Jiang; Chunli Su; Han Geng; Yanxin Wang; Weili Ge; Hongjie Pan; Xianjun Xie; Guojie Feng (Water Research, 2025)

Long-term manure and mineral fertilisation drive distinct pathways of soil organic nitrogen decomposition: Insights from a 180-year-old study - Wankun Pan; Sheng Tang; Jingjie Zhou; Wolfgang Wanek; Andrew S. Gregory; Tida Ge; Karina A. Marsden; David R. Chadwick; Yongchao Liang; Lianghuan Wu; Qingxu Ma; Davey L. Jones (Soil Biology and Biochemistry, 2025)

Isolation, purification, and heterologous expression of a novel protein with anti-proliferative activity from Sanghuangporus vaninii mycelia - Jiaxin Ge; Chaoxia Wang; Jiashi Pan; Siqi Zheng; Yunxiang Liang; Yuxia Mei (Food Research International, 2025)

A point-of-care SERS-based microdevice for multi-pesticide poisoning diagnostics towards first aid scenarios - Meng Jin; Hui Pan; Ge Gao; Mengping Zhang; Haiyan Wei; Xiao Meng; Wenwen Chen; Xinya Zhang; Ming Shang; Cuijuan Wang (Chemical Engineering Journal, 2025)

Recyclable flame retardant, luminescent, and transparent thermoplastic polyurethanes: applications in light conversion films for flexible solar cells - Li-Wei Su; Ming-Hao Liu; Yang Jing; Peng-Yu Huang; Bo Jiang; Rui-Guang Xing; Xin Ge; Ya-Hui Li; Jin-Xiao Bao; Gao-Fei Pan (Chemical Engineering Journal, 2025)

Coupling soil bacterial and fungal community traits to multifunctionality in grassland ecosystem - Chenxiao Ding; Yaowei Liu; Marcela Hernández; Han Sun; Shuo Jiao; Hong Pan; Tida Ge; Kankan Zhao; Qichun Zhang; Jianming Xu; Yong Li (Agriculture, Ecosystems & Environment, 2025)

Two undescribed coumarins from Hansenia weberbaueriana - Yixiao Pan; Mengdan Liu; Yunjie Hu; Chenyi Yan; Dale Guo; Ge Kuang (Natural Product Research, 2025)

Novel insights into the DOM-driven processes affecting nitrogen cycling in shallow aquifers of the West Liao River Plain: Evidence from FT-ICR MS and isotope analyses - Jiaqi Jiang; Chunli Su; Han Geng; Yanxin Wang; Weili Ge; Hongjie Pan; Xianjun Xie; Guojie Feng (Journal of Hydrology, 2025)

Novel strategy for screening aptamers of Staphylococcus aureus enterotoxin A based on active fragments and fusion design - Shujing Ge; Mengyao Guan; Fei Pan; Yanli Wang; Daodong Pan; Chaoying Zhang; Xinchang Gao; Yali Dang (Analytica Chimica Acta, 2025)

Macrofaunal biodiversity and trophic structure varied in response to changing environmental properties along the Spartina alterniflora invasion stages - Li Yang; Rui Pan; Shuang Wang; Zhangyan Zhu; Hongshan Li; Ruiping Yang; Xiaoping Sun; Baoming Ge (Marine Pollution Bulletin, 2025)

Decadal water management measures moderated the subsidence of North China Plain - Hang Xu; Man Li; Teng Wang; Daqing Ge; Yun Pan (Science Bulletin, 2025)

The role of ATG7-mediated ferroptosis in formaldehyde-induced ovarian injury in rats - Kun Mao; Hao-zhe Yan; Jia-qi Yang; Zi-xin Yin; Xin-qi Gao; Hao-fu Liu; Heng Su; Yuan-yuan Geng; Pan Ge; Dang-xia Zhou (Reproductive Toxicology, 2025)

Hierarchical Cu-doped MoS2 microspheres with efficient visible-light-driven peroxymonosulfate activation for micropollutant degradation: Nanostructure engineering and reaction mechanism - Bao Pan; Ge Jin; Wen Chen; Jiani Qin; Fei Li; Chuanyi Wang (Environmental Research, 2025)

Construction of site-specific immobilized lipase in bio-inspired “rigid and flexible” composite PVIm/ZIF-8 for long-cycle biodiesel synthesis from waste cooking oil - Qian Wang; Xinyuan Zheng; Meiling Ge; Rong Chen; Fangpei Ma; Jianming Pan; Fu Yang (Chemical Engineering Journal, 2025)

Gut microbiota and metabolic profile affected by pectic domains during in vitro rat fecal fermentation: A comparative study between different glycans rich in pectic monosaccharides - Yuanyuan Zhao; Pan Wang; Dan Wang; Wenting Zhao; Junjuan Wang; Zhiwen Ge; Ye Liu; Xiaoyan Zhao (Carbohydrate Polymers, 2025)

Associations between air pollutants and emergency ambulance dispatches for all-cause and nervous system disease in China Qingdao: a time-stratified case-crossover study - Yang Yu; Bingling Wang; Lu Pan; Nan Ge; Xiaocheng Gu; Yuan Fang; Hua Zhang; Jianjun Zhang; Yan Ma; Haiping Duan (Environmental Monitoring and Assessment, 2025)

Ultrathin zwitterionic COF membranes from colloidal 2D-COF towards precise molecular sieving - Xinliang Zhang; Xueting Zhao; Jinshan Sun; Yubin He; Bin Wu; Liang Ge; Jiefeng Pan (Water Research, 2025)

Study on the hydrodynamic characteristics of an outboard engine propeller with hydrophobic coating - Xiaoqing Tian; Haofan Ge; Huachen Pan; Ming Lv; Zefei Zhu; Hao Xu; Jianxing Leng; Chizhong Wang (Ocean Engineering, 2025)

MOF@Ag/AAB/Au@Ag composite matrix full-dimensional divergence effect-based SERS paper sensor for rapid carbaryl quantification - Yujie Pan; Peini Zhao; Weili Cai; Hehe Fang; Xiaoru Wang; Junyu Zhao; Peihua Zhu; Hongmei Yang; Shenguang Ge; Jinghua Yu (Food Chemistry, 2025)

Chemical characterization and classification of vegetable oils using DESI-MS coupled with a neural network - Yiwei Cui; Liangcun Zhu; Yan Li; Kai Ge; Weibo Lu; Lijun Ge; Kang Chen; Jing Xue; Feiyang Zheng; Shuncong Dai; Huafei Pan; Jingjing Liang; et al. (Food Chemistry, 2025)

The Role of ICP Monitoring in Minimally Invasive Surgery for the Management of Intracerebral Hemorrhage - Ge Zhang; Yunjie Li; Danyang Chen; Zhuojin Wu; Chao Pan; Ping Zhang; Xingwei Zhao; Bo Tao; Han Ding; Cai Meng; Diansheng Chen; Wenjie Liu; et al. (Translational Stroke Research, 2025)
Intracerebral hemorrhage (ICH) is the second major stroke type, with high incidence, high disability rate, and high mortality. At present, there is no effective and reliable treatment for ICH. As a result, most patients have a poor prognosis. Minimally invasive surgery (MIS) is the fastest treatment method to remove hematoma, which is characterized by less trauma and easy operation. Some studies have confirmed the safety of MIS, but there are still no reports showing that it can significantly improve the functional outcome of ICH patients. Intracranial pressure (ICP) monitoring is considered to be an important part of successful treatment in traumatic brain diseases. By monitoring ICP in real time, keeping stable ICP could help patients with craniocerebral injury get a good prognosis. In the course of MIS treatment of ICH patients, keeping ICP stable may also promote patient recovery. In this review, we will take ICP monitoring as the starting point for an in-depth discussion.

An exact equation for the average interparticle forces at contacts with similar orientations in granular materials - Ge Duan; Chaofa Zhao; Kun Pan; Yanni Chen (Computers and Geotechnics, 2025)

Geopolymer armor-reinforced composite membranes for efficient oil–water separation and dye degradation - Chunyan Huang; Zichen Li; Yuning Pan; Zhili Li; Yuanyuan Ge (Chemical Engineering Journal, 2025)

circTP63-N suppresses the proliferation and metastasis of nasopharyngeal carcinoma via engaging with HSP90AB1 to modulate the YAP1/Hippo signaling pathway - Dan Wang; Sicheng Zuo; Junshang Ge; Hongke Qu; Jie Wu; Na Yi; Lei Shi; Yumin Wang; Yongzhen Mo; Chunmei Fan; Yi He; Pan Chen; et al. (Science China Life Sciences, 2025)

Occurrence, Removal, and Ecological and Human Health Risk Assessment of 18 Endocrine Disrupting Compounds in Wastewater Treatment Plants in Nanjing, China - Lichao Tan; Fukai Tang; Keke Xu; Mingzhu Zhang; Xiaoyan Zhang; Jingjing Yun; Baoliu Pan; Kegui Zhang; Deyang Kong; Feng Ge (Bulletin of Environmental Contamination and Toxicology, 2025)

Pathogenicity comparison between porcine G9P[23] and G5P[23] RVA in piglets - Zixin Li; Yudi Pan; Yanxiang Zhou; Jianshuang Cui; Hailiang Ge; Wei Zhao; Li Feng; Jin Tian (Veterinary Microbiology, 2025)

Environmental DNA integrity index is sensitive for species biomass estimation in freshwater - Qinyu Ge; Yanyan Piao; Zhihui Li; Yuwei Yang; Min Pan; Yunfei Bai (Science of The Total Environment, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Far-field response to the closure of the Meso-Tethys Ocean: New geochronological evidence from the Chem Co graben in the westernmost part of Central Tibet - Yong Zheng; Jiawei Pan; Haibing Li; Zuolin Tian; Dongliang Liu; Mingkun Bai; Shuai Han; Chenglong Ge; Haijian Lu; Ning Zhong (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Three-dimensional oriented Ca nanoporous carbon with N doping tuned via self-assembly to potentiate P adsorption: The vital role of the micro interfacial electronic environment - Yibo Zhang; Jun Nan; Fangmin Wu; Xuesong Ye; Zhencheng Ge; Li He; Yanhan Che; Han Deng; Yunhao Pan; Bohan Liu (Journal of Cleaner Production, 2025)

Corrigendum to “Responses of geomorphic indices to the northward migration of the Eastern Himalayan syntaxis” [Geomorphology 465 (2024) 109396] - Xuemin Pan; Xiaoming Shen; Zhiyuan He; Xiaoping Yuan; Yukui Ge; Xiong Wu; Yingying Jia; Yanglin Zhao; Xiudang Tang (Geomorphology, 2025)

Antibacterial capacity and mechanism of the metabolites from two vaginal Lactobacillus strains - Jun Meng; Pan-Pan Dong; Xiang-Ge Xin; Yue Meng; Chang-He Ding; Jun Xi (Food Bioscience, 2025)

Exploring Time-Lag Effects of Water Buffering in Wetland Soils on Vegetation Dynamics - Ying-Ying Hao; Yi-Wen Pan; Jun-Yi Zheng; Gang Ge; Bin Zhao (Wetlands, 2025)

Changes in selenium bioavailability in selenium-enriched paddy soils induced by different water management and organic amendments - Haotian Gong; Hui Zhai; Yujian Wang; Lei Pan; Yumeng Liu; Yunshu Zhang; Huawei Shao; Guangmu Tang; Chunhui Ge; Wanli Xu; Min Wang (Science of The Total Environment, 2024)

Prediction and pathway models for assessing soil properties influencing soil selenium enrichment and bioavailability in Aksu Prefecture, northwest China - Hui Zhai; Yunshu Zhang; Wanli Xu; Wenyu Hou; Guangmu Tang; Chunhui Ge; Huawei Shao; Haotian Gong; Yujian Wang; Yumeng Liu; Lei Pan; Li Ling (Science of The Total Environment, 2024)

Image recognition enhances efficient monitoring of the coagulation-settling in drinking water treatment plants - Hongbo Liu; Yang Chen; Xuwei Pan; Junbo Zhang; Jianhong Huang; Eric Lichtfouse; Gang Zhou; Haiyu Ge (Journal of Cleaner Production, 2024)

Gel properties of curcumin-fortified Lactobacillus helveticus MB2-1 fermented milk and its gastrointestinal digestion in vitro - Zhiwen Ge; Dan Wang; Mingsheng Dong; Wenting Zhao; Pan Wang; Peiyou Qin; Xiaoyan Zhao (International Dairy Journal, 2024)

Understanding the factors influencing high-temperature Daqu from different geographical regions - Zhendong Zhang; Yaolan Meng; Yurong Wang; Qiangchuan Hou; Haibo Zhang; Ming Zhang; Ge Hu; Yingying Zhou; Qifu Pan; Zhuang Guo (Food Bioscience, 2024)

Eco-friendly nanotechnology in rheumatoid arthritis: ANFIS-XGBoost enhanced layered nanomaterials - Zhiyong Zhang; Mingtao Ye; Yisu Ge; Mohamed Gamal Elsehrawy; Xiaotian Pan; Nermeen Abdullah; Samia Elattar; Ehab El Sayed Massoud; Suxian Lin (Environmental Research, 2024)

Advancing the translation of vitrification strategies to whole porcine knee meniscus - Ge Pan; Peng Chen; Dustin Mueller; Marshall Wilson; Shuchun Sun; Zhenzhen Chen; Thomas Lee; Brooke Damon; Glenn Hepfer; Cherice Hill; Yongren Wu; Kelvin G.M. Brockbank; et al. (Cryobiology, 2024)

Ice-free cryopreservation of viable temperomandibular joint disc in a pig model - Dustin Mueller; Marshall Wilson; Ge Pan; Shangping Wang; Hai Yao (Cryobiology, 2024)

Tripartite-motif 3 represses ovarian cancer progression by downregulating lactate dehydrogenase A and inhibiting AKT signaling - Yu Cong; Xin Cui; Yaqian Shi; Xinxing Pan; Ke Huang; Zhe Geng; Pengfei Xu; Lili Ge; Jin Zhu; Juan Xu; Xuemei Jia (Molecular and Cellular Biochemistry, 2024)

The effect of pre-existing structures on the Cenozoic rifting processes: Insights from seismic reflection imaging of the northeastern south China sea - Zongdong Pan; Shaoping Lu; Hongfang Gao; Qing He; Han Chen; Xiao Ge (Journal of Structural Geology, 2024)

Responses of geomorphic indices to the northward migration of the Eastern Himalayan syntaxis - Xuemin Pan; Xiaoming Shen; Zhiyuan He; Xiaoping Yuan; Yukui Ge; Xiong Wu; Yingying Jia; Yanglin Zhao; Xiudang Tang (Geomorphology, 2024)

Different microbiota modulation and metabolites generation of five dietary glycans during in vitro gut fermentation are determined by their monosaccharide profiles - Yuanyuan Zhao; Yubin Wang; Qiancheng Ma; Dan Wang; Qianqian Jiang; Pan Wang; Zhiwen Ge; Junjuan Wang; Peiyou Qin; Xiaoyan Zhao (Food Research International, 2024)

Simultaneous detection of eight dairy-derived components using multiplex PCR combined with gene membrane chip - Yafang Huang; Yingqiu Pan; Huili Xia; Xinyu Ma; Siling Ding; Jian Ge; Junfang Jiang; Feng Guan (Food Control, 2024)

Sustainable utilization of mining resources: Exploring the impact of FinTech on green development from the perspective of mining enterprises - Wenfeng Ge; Ping Yang; Xu Pan; Qiying Ran (Resources Policy, 2024)

Research on a harmless treatment method for oily sludge in coal chemical wastewater and the pollutant transformation mechanism of oily sludge during the treatment process - Qian Ge; Yongjun Liu; Pan Liu; Zhuangzhuang Yang; Lu Yang; Zhe Liu; Zhihua Li (Journal of Hazardous Materials, 2024)

Anti-obesity effects of Lactiplantibacillus plantarum BHP03 on high-fat diet mice and its regulatory function on intestinal microbiota - Jun Meng; Pan-Pan Dong; Meng-Xi Zhu; Zheng Zhang; Jia-Hui Chen; Yue Meng; Chang-He Ding; Han Du; Dong-Ge Zheng; Ling-Guang Du (Food Bioscience, 2024)

Effects of environmental temperature extremes exposure on sperm quality - Evidence from a prospective cohort study in Anhui Province, China - Xu Zhang; Dongmei Ji; Ying Zhang; Liru Ge; Siwen Xu; Yongzhen Peng; Xuyang Chen; Jianping Ni; Guosheng Wang; Yubo Ma; Faming Pan (Environmental Research, 2024)

Application of expectation–maximization algorithm to estimate random walk process noise for GNSS tropospheric delay - Xinggang Zhang; Pan Li; Miaomiao Wang; Maorong Ge; Harald Schuh (GPS Solutions, 2024)

Levels, sources, and health risk assessment of phthalate acid esters in indoor dust of various microenvironments in university - Jun Pan; Xin Li; Ping Ding; Haojie Luo; Sha Cai; Qing Ge; Liuyi Zhang; Guocheng Hu (Chemosphere, 2024)

Beta-blocker drives the conjugative transfer of multidrug resistance genes in pure and complex biological systems - Qian Wu; Ge-Ge Wu; Kai-Nan Pan; Xue-Ping Wang; Hong-Yan Li; Zhe Tian; Ren-Cun Jin; Nian-Si Fan (Journal of Hazardous Materials, 2024)

The novel hydrolase IpcH initiates the degradation of isoprocarb in a newly isolated strain Rhodococcus sp. D-6 - Qian Zhu; Hongfei Liu; Kaihua Pan; Wanhe Zhu; Yihui Qiao; Qian Li; Junqiang Hu; Mingliang Zhang; Jiguo Qiu; Xin Yan; Jing Ge; Qing Hong (Journal of Hazardous Materials, 2024)

Constraints of geomorphic indices on the expansion mode of the southeastern margin of the Tibetan plateau - Xiong Wu; Xiaoming Shen; Zhiyuan He; Xiaoping Yuan; Yukui Ge; Xuemin Pan; Yingying Jia; Xiudang Tang; Yanglin Zhao (Journal of Asian Earth Sciences, 2024)

One-pot tandem conversion of furfural to γ-valerolactone over a series of modified zirconium-based metal–organic frameworks with variational Lewis and Brønsted acid sites - Wei Xue; Mingwei Ma; Pan Hou; Peng Zhang; Wenzheng Liu; Yongchen Liu; Huijuan Yue; Xiaofeng Wang; Ge Tian; Shouhua Feng (Fuel, 2024)

The optimization of in situ exopolysaccharides production in Lactobacillus helveticus MB2-1 fermented milk and its functional characteristics in vitro - Zhiwen Ge; Dan Wang; Fidelis Azi; Wenting Zhao; Pan Wang; Mingsheng Dong; Junjuan Wang; Yuanyuan Zhao; Xiaoyan Zhao (International Dairy Journal, 2024)

Influence of increasing acclimation temperature on growth, digestion, antioxidant capacity, liver transcriptome and intestinal microflora of Ussruri whitefish Coregonus ussuriensis Berg - Kaibo Ge; Ze Fan; Tianqing Huang; Wei Gu; Gaochao Wang; Enhui Liu; Runlei Pan; Datian Li; Yunchao Sun; Zuochun Yao; Liwei Wang; Cheng Zhao; et al. (Fish & Shellfish Immunology, 2024)

A computational efficient approach for multi-GNSS real-time precise clock estimation with undifferenced ambiguity resolution - Xiang Zuo; Pan Li; Bobin Cui; Maorong Ge; Harald Schuh (Journal of Geodesy, 2024)

Machine learning prediction of health risk and spatial dependence of geogenic contaminated groundwater from the Hetao Basin, China - Peng Xia; Yifu Zhao; Xianjun Xie; Junxia Li; Kun Qian; Haoyu You; Jingxian Zhang; Weili Ge; Hongjie Pan; Yanxin Wang (Journal of Geochemical Exploration, 2024)

Ablated Sonic Hedgehog Signaling in the Dentate Gyrus of the Dorsal and Ventral Hippocampus Impairs Hippocampal-Dependent Memory Tasks and Emotion in a Rat Model of Depression - Yan Luo; Yan Wang; Feng Qiu; Guanghan Hou; Jian Liu; Hui Yang; Mei Wu; Xuanqi Dong; Dongwei Guo; Ziyan Zhong; Xi Zhang; Jinwen Ge; et al. (Molecular Neurobiology, 2024)

Adaptation of a prey population to increasing predation risks - Ling Pan; Han Zhu; Yan Wang; Bao-Chun Shi; Xin-Feng Cheng; Ya-Li Ge; Xian-Ling Xiang; Xin-Li Wen; Yi-Long Xi (Hydrobiologia, 2024)

Active landslide detection using integrated remote sensing technologies for a wide region and multiple stages: A case study in southwestern China - Huiyan Lu; Weile Li; Qiang Xu; Wenlong Yu; Shengsen Zhou; Zhigang Li; Weiwei Zhan; Weimin Li; Shanmiao Xu; Pan Zhang; Xiujun Dong; Jingtao Liang; et al. (Science of The Total Environment, 2024)

Draconibacterium aestuarii sp.nov., a Glycolipid-Producing Bacterium Isolated from Tidal Flat Sediment and Emended Description of the Genus Draconibacterium - Jia-Yan Wang; Sha-Sha Qiu; Yue Su; Wei-Yu Pan; Tao Wang; Wen-Wu Zhang; Ge-Yi Fu; Min Wu (Current Microbiology, 2024)

Employing machine learning to predict the occurrence and spatial variability of high fluoride groundwater in intensively irrigated areas - Zhou Xiangcao; Chunli Su; Xie Xianjun; Weili Ge; Ziyi Xiao; Liangping Yang; Hongjie Pan (Applied Geochemistry, 2024)

The metabolic activation of pentachlorophenol to chloranil as a potent inhibitor of human and rat placental 3β-hydroxysteroid dehydrogenases - Weibing Zhang; Ming Su; Hao Lin; Chengshuang Pan; Yunbing Tang; Ren-shan Ge; Qianjin Fei (Toxicology Letters, 2024)

Structure-activity relationship and mechanistic study of organotins as inhibitors of human, pig, and rat gonadal 3β-hydroxysteroid dehydrogenases - Peiyu Wang; Zhongyao Ji; Huiqian Chen; Sailing Chen; Chengshuang Pan; Qianjin Fei; Ren-shan Ge; Ping Duan; Linxi Li (Toxicology and Applied Pharmacology, 2024)

An atmospheric water harvesting system based on the “Optimal Harvesting Window” design for worldwide water production - Qian Li; Zhao Shao; Qihong Zou; Quanwen Pan; Yao Zhao; Yaohui Feng; Wenwen Wang; Ruzhu Wang; Tianshu Ge (Science Bulletin, 2024)

Spatiotemporal heterogeneity in global urban surface warming - Shuang Ge; Wenfeng Zhan; Shasha Wang; Huilin Du; Zihan Liu; Chenguang Wang; Chunli Wang; Sida Jiang; Pan Dong (Remote Sensing of Environment, 2024)

Significant contribution of carbonyls to atmospheric oxidation capacity (AOC) during the winter haze pollution over North China Plain - Xue Yang; Gen Zhang; Guang Pan; Guolan Fan; Houyong Zhang; Xuan Ge; Mingyue Du (Journal of Environmental Sciences, 2024)

Effects of significant emission changes on PM2.5 chemical composition and optical properties from 2019 to 2021 in a typical industrial city of eastern China - Xiangpeng Huang; Changping Li; Chao Pan; Yue'e Li; Wei Zheng; Guangwu Lin; Haiwei Li; Yunjiang Zhang; Junfeng Wang; Yali Lei; Jianhuai Ye; Xinlei Ge; et al. (Atmospheric Research, 2024)

Generation estimation and critical metals quantity assessment of retired mobile phones in Japan - Ang Li; Bo Li; Ge Yang; Kronnaphat Khumvongsa; Jingjin Pan; Xiaolong Song; Xuyang Lei; Suxia Hou; Dong Yang; Bin Lu (Journal of Cleaner Production, 2024)

Rational design of complex quantum dots decorated ceria nanorods for efficient visible-light driven nitrogen fixation - Huaiwei Zhang; Liang Bao; Ying Pan; Dihua Wu; Jingyuan Ge (Journal of Environmental Chemical Engineering, 2024)

Predictions of air quality and challenges for eliminating air pollution during the 2022 Olympic Winter Games - Wenyi Yang; Qizhong Wu; Jie Li; Xueshun Chen; Huiyun Du; Zhe Wang; Dongqing Li; Xiao Tang; Yele Sun; Zhilan Ye; Xiaole Pan; Baozhu Ge; et al. (Atmospheric Research, 2024)

Agarose amplification based sequencing characterization cell-free RNA in preimplantation spent embryo medium - Huajuan Shi; Qinyu Ge; Min Pan; Yuqi Sheng; Ting Qi; Ying Zhou; Yuqing Sun; Yunfei Bai; Lingbo Cai (Analytica Chimica Acta, 2024)

Acid tolerance response of Salmonella during the squid storage and its amine production capacity analysis - Wei Ge; Qiong Yang; Hui Wang; Chuanyan Pan; Min Lv; Lingyun Liang; Shiya Ya; Xu Luo; Weisheng Wang; Huawei Ma (Archives of Microbiology, 2024)

Towards standardizing automated image analysis with artificial intelligence for biodiversity - Peng Zhou; Yu-Xin Bu; Ge-Yi Fu; Chun-Sheng Wang; Xue-Wei Xu; Xiaoyong Pan (Frontiers in Marine Science, 2024)

Machine learning revealing key factors influencing HONO chemistry in Beijing during heating and non-heating periods - Wenqian Zhang; Shengrui Tong; Siqi Hou; Pusheng Zhao; Yuepeng Pan; Lili Wang; Mengtian Cheng; Dongsheng Ji; Guiqian Tang; Bo Hu; Xin Li; Maofa Ge (Atmospheric Research, 2024)

Anaerobic granular sludge performance in an expanded granular sludge bed reactor treating calcium-rich wastewater by adjusting CaCO3 crystallization: Effect of upflow velocity and Ca2+ concentration - Xiaoji Liu; Dongning Pan; Quan Yuan; Xiyuan Feng; Meixuan Li; Xuening Song; Meiling Li; Yajuan Ge; Yukun Xing; Yuanzhou Yu; Zhengyu Jin (Science of The Total Environment, 2024)

Self-polarization-enhanced oxygen evolution reaction by flower-like core–shell BaTiO3@NiFe-layered double hydroxide heterojunctions - Shuang Wang; Kai Ge; He Cui; Shunli Li; Yongfang Yang; Mingwang Pan; Lei Zhu (Chemical Engineering Journal, 2024)

Interfacial synergy between Pt3Co nanoparticles and CoO for efficient ammonia borane hydrolysis - Ruichao Xu; Hongmei Li; LiuXin Xu; Ya Pan; Min Ge; Chao Wang; Zhihu Sun (Chemical Engineering Journal, 2024)

White rice consumption and risk of cardiometabolic and cancer outcomes: A systematic review and dose-response meta-analysis of prospective cohort studies - Honghao Lai; Mingyao Sun; Yafei Liu; Hongfei Zhu; Mengting Li; Bei Pan; Qi Wang; Qiuyu Yang; Xiao Cao; Chen Tian; Yao Lu; Xuping Song; et al. (Critical Reviews in Food Science and Nutrition, 2023)

Lysosomal dysfunction in carbon black-induced lung disorders - Mingtong Gao; Xiao Ge; Yun Li; Gege Zheng; Jun Cai; Jiani Yao; Tianyi Wang; Yichang Gao; Yuchen Yan; Yinming Chen; Yang Pan; Po Hu (Science of The Total Environment, 2023)

Explosion behaviors of hydrogen-nitrous oxide mixtures with propane addition - Yun Ge; Hong-Hao Ma; Jia-Wei Liu; Yuan Zeng; Jun Pan; Lu-Qing Wang (Fuel, 2023)

Soil legacy nutrients contribute to the decreasing stoichiometric ratio of N and P loading from the Mississippi River Basin - Zihao Bian; Hanqin Tian; Shufen Pan; Hao Shi; Chaoqun Lu; Christopher Anderson; Wei‐Jun Cai; Charles S. Hopkinson; Dubravko Justic; Latif Kalin; Steven Lohrenz; Steven McNulty; et al. (Global Change Biology, 2023)
Human‐induced nitrogen–phosphorus (N, P) imbalance in terrestrial ecosystems can lead to disproportionate N and P loading to aquatic ecosystems, subsequently shifting the elemental ratio in estuaries and coastal oceans and impacting both the structure and functioning of aquatic ecosystems. The N:P ratio of nutrient loading to the Gulf of Mexico from the Mississippi River Basin increased before the late 1980s driven by the enhanced usage of N fertilizer over P fertilizer, whereafter the N:P loading ratio started to decrease although the N:P ratio of fertilizer application did not exhibit a similar trend. Here, we hypothesize that different release rates of soil legacy nutrients might contribute to the decreasing N:P loading ratio. Our study used a data‐model integration framework to evaluate N and P dynamics and the potential for long‐term accumulation or release of internal soil nutrient legacy stores to alter the ratio of N and P transported down the rivers. We show that the longer residence time of P in terrestrial ecosystems results in a much slower release of P to coastal oceans than N. If contemporary nutrient sources were reduced or suspended, P loading sustained by soil legacy P would decrease much slower than that of N, causing a decrease in the N and P loading ratio. The longer residence time of P in terrestrial ecosystems and the increasingly important role of soil legacy nutrients as a loading source may explain the decreasing N:P loading ratio in the Mississippi River Basin. Our study underscores a promising prospect for N loading control and the urgency to integrate soil P legacy into sustainable nutrient management strategies for aquatic ecosystem health and water security.

Plant and animal positive-sense single-stranded RNA viruses encode small proteins important for viral infection in their negative-sense strand - Pan Gong; Qingtang Shen; Mingzhen Zhang; Rui Qiao; Jing Jiang; Lili Su; Siwen Zhao; Shuai Fu; Yu Ma; Linhao Ge; Yaqin Wang; Rosa Lozano-Durán; et al. (Molecular Plant, 2023)

Distribution of mudsnail Bullacta caurina along smooth cordgrass Spartina alterniflora invasion stages on a coast of the Yellow Sea, China - Li Yang; Jingyi Shi; Rui Pan; Ruiping Yang; Hongshan Li; Shuang Wang; Baoming Ge (Marine Environmental Research, 2023)

Non-invasive prediction of mango quality using near-infrared spectroscopy: Assessment on spectral interferences of different packaging materials - Fangchen Ding; Changzhou Zuo; Juan Francisco García-Martín; Yan Ge; Kang Tu; Jing Peng; Hongmei Xiao; Weijie Lan; Leiqing Pan (Journal of Food Engineering, 2023)

Potential role of cell wall pectin polysaccharides, water state, and cellular structure on twice “increase–decrease” texture changes during kohlrabi pickling process - Zhixuan Yang; Hekai Fan; Ruoxuan Li; Bowen Li; Jiangtao Fan; Jinjiang Ge; Xiaoyun Xu; Siyi Pan; Fengxia Liu (Food Research International, 2023)

Rapid adaptation of a rotifer prey population to non-consumptive predation pressures - Ling Pan; Han Zhu; Yi-Long Xi; Xin-Feng Cheng; Ya-Li Ge; Xian-Ling Xiang; Xin-Li Wen (Hydrobiologia, 2023)

Temporal-spatial Generation of Astrocytes in the Developing Diencephalon - Wentong Hong; Pifang Gong; Xinjie Pan; Zhonggan Ren; Yitong Liu; Guibo Qi; Jun-Liszt Li; Wenzhi Sun; Woo-Ping Ge; Chun-Li Zhang; Shumin Duan; Song Qin (Neuroscience Bulletin, 2023)
Astrocytes are the largest glial population in the mammalian brain. However, we have a minimal understanding of astrocyte development, especially fate specification in different regions of the brain. Through lineage tracing of the progenitors of the third ventricle (3V) wall via in-utero electroporation in the embryonic mouse brain, we show the fate specification and migration pattern of astrocytes derived from radial glia along the 3V wall. Unexpectedly, radial glia located in different regions along the 3V wall of the diencephalon produce distinct cell types: radial glia in the upper region produce astrocytes and those in the lower region produce neurons in the diencephalon. With genetic fate mapping analysis, we reveal that the first population of astrocytes appears along the zona incerta in the diencephalon. Astrogenesis occurs at an early time point in the dorsal region relative to that in the ventral region of the developing diencephalon. With transcriptomic analysis of the region-specific 3V wall and lateral ventricle (LV) wall, we identified cohorts of differentially-expressed genes in the dorsal 3V wall compared to the ventral 3V wall and LV wall that may regulate astrogenesis in the dorsal diencephalon. Together, these results demonstrate that the generation of astrocytes shows a spatiotemporal pattern in the developing mouse diencephalon.

Transport model simulation prediction and environmental risk assessment of pyrethroid insecticides in urban artificial lakes caused by rainfall: A case study of Cloud Mountain Park in subhumid climate zone - Siyao Liu; Xuanying Li; Rui Ding; Yuwen Pan; Xiaoyu Ge; Weifang Ma (Journal of Environmental Management, 2023)

Refractory black carbon aerosols in rainwater in the summer of 2019 in Beijing: Mass concentration, size distribution and wet scavenging ratio - Shandong Lei; Baozhu Ge; Hang Liu; Jiannong Quan; Danhui Xu; Yuting Zhang; Weijie Yao; Lu Lei; Yu Tian; Qi Liao; Xiaoyong Liu; Jie Li; et al. (Journal of Environmental Sciences, 2023)

Halogenated bisphenol A derivatives potently inhibit human, rat, and mouse gonadal 3β-hydroxysteroid dehydrogenases: Structure-activity relationship and in silico molecular docking analysis - Yang Yu; Mengyun Wang; Ya Chen; Chengshuang Pan; Qianjin Fei; Yang Zhu; Huitao Li; Ren-shan Ge (Toxicology Letters, 2023)

GRPR down-regulation inhibits spermatogenesis through Ca2+ mediated by PLCβ/IP3R signaling pathway in long-term formaldehyde-exposed rats - Yan-qi Yang; Rui-fang Sun; Pan Ge; Wen-Xing Li; Xiang Zhang; Jian Zhang; Lu Ye; Nan Zhang; Si-yu Wang; Mo-qi Lv; Dang-xia Zhou (Food and Chemical Toxicology, 2023)

Corrigendum to “Rno_circRNA_006061 participates in apoptosis induced by formaldehyde via activating p38/ATF3 pathway” [Chem. Biol. Interact. 381 (2023) 110584] - Pan Ge; Xue-wei Yuan; Xiang Zhang; Zhi-hao Liu; Si-yu Wang; Yan-qi Yang; Qian-nan Wang; Li-jian Qian; Ya-zhao Li; Dang-xia Zhou (Chemico-Biological Interactions, 2023)

Surgical Robotics for Intracerebral Hemorrhage Treatment: State of the Art and Future Directions - Zhuojin Wu; Danyang Chen; Chao Pan; Ge Zhang; Shiling Chen; Jian Shi; Cai Meng; Xingwei Zhao; Bo Tao; Diansheng Chen; Wenjie Liu; Han Ding; et al. (Annals of Biomedical Engineering, 2023)
Intracerebral hemorrhage (ICH) is a stroke subtype with high mortality and disability, and there are no proven medical treatments that can improve the functional outcome of ICH patients. Robot-assisted neurosurgery is a significant advancement in the development of minimally invasive surgery for ICH. This review encompasses the latest advances and future directions of surgical robots for ICH. First, three robotic systems for neurosurgery applied to ICH are illustrated. Second, the key technologies of robot-assisted surgery for ICH are introduced in aspects of stereotactic technique and navigation, the puncture instrument, and hematoma evacuation. Finally, the limitations of current surgical robots are summarized, and the possible development direction is discussed, which is named “multisensor fusion and intelligent aspiration control of minimally invasive surgical robot for ICH”. It is expected that the new generation of surgical robots for ICH will facilitate quantitative, precise, individualized, standardized treatment strategies for ICH.

Hepatotoxicity screening and ranking of structurally different pyrrolizidine alkaloids in zebrafish - Yueyang Pan; Jiang Ma; Hui Zhao; Peter P. Fu; Ge Lin (Food and Chemical Toxicology, 2023)

Rno_circRNA_006061 participates in apoptosis induced by formaldehyde via activating p38/ATF3 pathway - Pan Ge; Xue-wei Yuan; Xiang Zhang; Zhi-hao Liu; Si-yu Wang; Yan-qi Yang; Qian-nan Wang; Li-jian Qian; Ya-zhao Li; Dang-xia Zhou (Chemico-Biological Interactions, 2023)

Role of TPEN in Amyloid-β25–35-Induced Neuronal Damage Correlating with Recovery of Intracellular Zn2+ and Intracellular Ca2+ Overloading - Wen-bo Chen; Yu-xiang Wang; Hong-gang Wang; Di An; Dan Sun; Pan Li; Tao Zhang; Wan-ge Lu; Yan-qiang Liu (Molecular Neurobiology, 2023)

Carbonaceous nanofibrous membranes with enhanced superhydrophilicity and underwater superoleophobicity for effective purification of emulsified oily wastewater - Hong Chen; Anqi Zhou; Yifan Zhang; Xueqin Wang; Gangwei Pan; Sijun Xu; Qixia Liu; Haoru Shan; Qiuxia Fu; Jianlong Ge (Chemical Engineering Journal, 2023)

Exogenous hydrogen sulphide alleviates nodule senescence in Glycine max-Sinorhizobium fredii symbiotic system - Juan Chen; Wu-Yu Liu; Xin Zhang; Qing Pan; Feng-Shuya Wang; Shi-Ming Wen; Jian-Hua Zhang; Ge-Hong Wei (Plant and Soil, 2023)

A new large-area hierarchical PPP-RTK service strategy - Bobin Cui; Xinyuan Jiang; Jungang Wang; Pan Li; Maorong Ge; Harald Schuh (GPS Solutions, 2023)
Introducing precise atmosphere information into precise point positioning enables rapid ambiguity resolution and introduces a significant accuracy improvement. However, it can only be implemented in regions with dense networks and stable communication links. For larger areas, e.g., an intercontinental level, there is a conflict between the accuracy of corrections and the amount of atmosphere information to be disseminated. We develop a hierarchical augmentation mode to combine the advantages of the fitting model and region interpolation model to relieve the communication burden. Relying on the fitting model with fewer coefficients applied over large areas as the essential information, the unmodeled errors are calculated at each reference station, and further correction information is optional compensation depending on the magnitude of the unmodeled residuals. We perform the proposed models on 103 EUREF Permanent Network stations with 200-km station spacing and 84 stations as the external validation. The ionosphere and troposphere fitting models have an average accuracy of about 4.2 and 1.3 cm, respectively, under meteorologically calm conditions. The unmodeled error transmission determined by the magnitude of residuals can be reduced by 61% and 96% for the ionospheric and tropospheric delays, respectively, with respect to the legacy interpolation mode. Further compensation implemented, i.e., unmodeled residuals, can achieve instantaneous convergence for 83.6% of all solutions, and the overall initialization time is within 1.0 min. Thus, the proposed hierarchical positioning mode satisfies real-time positioning convergence requirements and significantly reduces massive corrections in communication.

Superior efficiency hydrogen peroxide production in acidic media through epoxy group adjacent to Co-O/C active centers on carbon black - Jili Yuan; Hao Yin; Xin Ge; Ronglan Pan; Caijuan Huang; Dechao Chen; Lin Hu; Haibo Xie (Chemical Engineering Journal, 2023)

LncRNA SLC25A21-AS1 increases the chemosensitivity and inhibits the progression of ovarian cancer by upregulating the expression of KCNK4 - Ke Huang; Xiyi Chen; Zhe Geng; Xueyou Xiong; Yu Cong; Xinxing Pan; Siyu Liu; Lili Ge; Juan Xu; Xuemei Jia (Functional & Integrative Genomics, 2023)

A framework for identifying the onset of landslide acceleration based on the exponential moving average (EMA) - Jia-zhu Wang; Neng-pan Ju; Yong-bo Tie; Yong-jian Bai; Hua Ge (Journal of Mountain Science, 2023)

Dissolved biochar fractions and solid biochar particles inhibit soil acidification induced by nitrification through different mechanisms - Ren-Yong Shi; Ni Ni; Ru-Hai Wang; Jackson Nkoh Nkoh; Xiao-Ying Pan; Ge Dong; Ren-Kou Xu; Xiu-Min Cui; Jiu-Yu Li (Science of The Total Environment, 2023)

Netrin-3 Suppresses Diabetic Neuropathic Pain by Gating the Intra-epidermal Sprouting of Sensory Axons - Weiping Pan; Xueyin Huang; Zikai Yu; Qiongqiong Ding; Liping Xia; Jianfeng Hua; Bokai Gu; Qisong Xiong; Hualin Yu; Junbo Wang; Zhenzhong Xu; Linghui Zeng; et al. (Neuroscience Bulletin, 2023)

Flexible SERS strip based on HKUST-1(cu)/biomimetic antibodies composite multilayer for trace determination of ethephon - Wenli Xiu; Peini Zhao; Yujie Pan; Xiaoru Wang; Lina Zhang; Shenguang Ge; Jinghua Yu (Analytica Chimica Acta, 2023)

Construction of ZnIn2S4/MOF-525 heterojunction system to enhance photocatalytic degradation of tetracycline - Xiansheng Zhang; Zhifeng Liu; Binbin Shao; Ting Wu; Yuan Pan; Songhao Luo; Miao He; Lin Ge; Jingwen Sun; Chunyun Cheng; Jian Huang (Environmental Science and Pollution Research, 2023)

EchoAI: A deep-learning based model for classification of echinoderms in global oceans - Zhinuo Zhou; Ge-Yi Fu; Yi Fang; Ye Yuan; Hong-Bin Shen; Chun-Sheng Wang; Xue-Wei Xu; Peng Zhou; Xiaoyong Pan (Frontiers in Marine Science, 2023)
Introduction In response to the need for automated classification in global marine biological studies, deep learning is applied to image-based classification of marine echinoderms. Methods Images of marine echinoderms are collected and classified according to their systematic taxonomy. The images belong to 5 classes, 38 orders, 145 families, 459 genera, and 1021 species, respectively. The deep learning model, EfficientNetV2, outperforms the competing model and is chosen for developing the automated classification tool, EchoAI. Then, the EfficientNetV2-based tool, EchoAI is applied to each taxonomic level. Results The accuracy for the test dataset was 0.980 (class), 0.876 (order), 0.738 (family), 0.612 (genus), and 0.469 (species), respectively. Online prediction service is provided. Discussion The EchoAI model and results are facilitated for investigating the diversity, abundance and distribution of species at the global scale, and the methodological strategy can also be applied to image classification of other categories of marine organisms, which is of great significance for global marine studies. EchoAI is freely available at http://www.csbio.sjtu.edu.cn/bioinf/EchoAI/ for academic use.

Zinc homeostasis may reverse the synergistic neurotoxicity of heavy metal mixtures in Caenorhabditis elegans - Haiqing Cai; Yu Bao; Hong Cheng; Xiaoting Ge; Mengdi Zhang; Xiuming Feng; Yuan Zheng; Junxiu He; Yue Wei; Chaoqun Liu; Longman Li; Lulu Huang; et al. (Science of The Total Environment, 2023)

Sulfur dioxide may predominate in the adverse effects of ambient air pollutants on semen quality among the general population in Hefei, China - Feng Zhang; Hang Li; Wenting Xu; Ge Song; Zhanpeng Wang; Xiaohong Mao; Yiqiu Wei; Mengyang Dai; Yuying Zhang; Qunshan Shen; Feifei Fu; Jing Tan; et al. (Science of The Total Environment, 2023)

Eliminating temporal correlation in quantum-dot entangled photon source by quantum interference - Run-Ze Liu; Yu-Kun Qiao; Han-Sen Zhong; Zhen-Xuan Ge; Hui Wang; Tung-Hsun Chung; Chao-Yang Lu; Yong-Heng Huo; Jian-Wei Pan (Science Bulletin, 2023)

Evaluating response mechanisms of soil microbiomes and metabolomes to Bt toxin additions - Lei Ge; Lili Song; Luyao Wang; Yujie Li; Yu Sun; Cui Wang; Jun Chen; Guogan Wu; Aihu Pan; Yunfei Wu; Zhexue Quan; Peng Li (Journal of Hazardous Materials, 2023)

Characteristics, chemical transformation and source apportionment of volatile organic compounds (VOCs) during wintertime at a suburban site in a provincial capital city, east China - BaoLin Wang; ZhenGuo Liu; ZiAng Li; YuChun Sun; Chen Wang; ChuanYong Zhu; Lei Sun; Na Yang; Ge Bai; GuoLan Fan; XiaoYan Sun; ZhiYong Xia; et al. (Atmospheric Environment, 2023)

GWAS across multiple environments and WGCNA suggest the involvement of ZmARF23 in embryonic callus induction from immature maize embryos - Tianhu Liang; Yu Hu; Na Xi; Minyan Zhang; Chaoying Zou; Fei Ge; Guangsheng Yuan; Shibin Gao; Suzhi Zhang; Guangtang Pan; Langlang Ma; Thomas Lübberstedt; et al. (Theoretical and Applied Genetics, 2023)

Random walk multipath method for Galileo real-time phase multipath mitigation - Mingxian Hu; Yibin Yao; Maorong Ge; Frank Neitzel; Junbo Shi; Peifen Pan; Meihao Yang (GPS Solutions, 2023)

SUMOylation-modified Pelota-Hbs1 RNA surveillance complex restricts the infection of potyvirids in plants - Linhao Ge; Buwei Cao; Rui Qiao; Hongguang Cui; Shaofang Li; Hongying Shan; Pan Gong; Mingzhen Zhang; Hao Li; Aiming Wang; Xueping Zhou; Fangfang Li (Molecular Plant, 2023)

Fine mapping and candidate gene analysis of qFL-A12-5: a fiber length-related QTL introgressed from Gossypium barbadense into Gossypium hirsutum - Xianghui Xiao; Ruixian Liu; Juwu Gong; Pengtao Li; Ziyin Li; Wankui Gong; Aiying Liu; Qun Ge; Xiaoying Deng; Shaoqi Li; Quanjia Chen; Hua Zhang; et al. (Theoretical and Applied Genetics, 2023)

Groundwater contamination source identification based on Sobol sequences–based sparrow search algorithm with a BiLSTM surrogate model - Yuanbo Ge; Wenxi Lu; Zidong Pan (Environmental Science and Pollution Research, 2023)

Coumaronochromones, flavanones, and isoflavones from the twigs and leaves of Erythrina subumbrans inhibit PTP1B and nitric oxide production - Cai-Ying Liu; Pan Deng; Bin Wang; Ai-Hong Liu; Meng-Ge Wang; Song-Wei Li; Li-Li Chen; Shui-Chun Mao (Phytochemistry, 2023)

Hyperforin: A natural lead compound with multiple pharmacological activities - Xin-Xin Li; Yu Yan; Jia Zhang; Kang Ding; Cong-Yuan Xia; Xue-Ge Pan; Yan-Jing Shi; Jie-Kun Xu; Jun He; Wei-Ku Zhang (Phytochemistry, 2023)

Hydrodynamics of liquid-liquid two-phase flow accounting for the coupling of dean vortices and Poiseuille flow - Shixiong Ge; Taoxian Zhang; Chun Tao; Weixing Huang; Dawei Pan (Chemical Engineering Journal, 2023)

A Method for Reducing Ocean Wave-Induced Magnetic Noises in Shallow-Water MT Data Using a Complex Adaptive Filter - Yunju Wu; Ming Luo; Yuguo Li; Jiaqi Ge; Lindong Pan (Journal of Ocean University of China, 2023)

Whole-genome sequencing and comparative genomic analysis of a pathogenic Enterocytozoon hepatopenaei strain isolated from Litopenaeus vannamei - Libao Wang; Hui Li; Wenjun Shi; Yi Qiao; Pan Wang; Zhijun Yu; Ran Zhao; Runhao Hu; Hui Shen; Jie Cheng; Ge Jiang; Xintong Huang; et al. (Aquaculture International, 2023)

Comprehensive profiles of per- and polyfluoroalkyl substances in Chinese and African municipal wastewater treatment plants: New implications for removal efficiency - Lulin Jiang; Jingzhi Yao; Ge Ren; Nan Sheng; Yong Guo; Jiayin Dai; Yitao Pan (Science of The Total Environment, 2023)

Screening of microalgae species and evaluation of algal-lipid stimulation strategies for biodiesel production - Yanan Yang; Shuhan Ge; Yitong Pan; Weiyi Qian; Shengnan Wang; Jian Zhang; Lin-Lan Zhuang (Science of The Total Environment, 2023)

Application of carbon aerogel-based materials in persulfate activation for water treatment: A review - Binbin Shao; Yuantao Xu; Zhifeng Liu; Ting Wu; Yuan Pan; Xiansheng Zhang; Miao He; Lin Ge; Yue Lu; Yang Liu; Weimin Zeng; Lin Tang (Journal of Cleaner Production, 2023)

Disinfection byproducts formation from emerging organic micropollutants during chlorine-based disinfection processes - Binbin Shao; Leyuan Shen; Zhifeng Liu; Lin Tang; Xiaofei Tan; Dongbo Wang; Weimin Zeng; Ting Wu; Yuan Pan; Xiansheng Zhang; Lin Ge; Miao He (Chemical Engineering Journal, 2023)

Association of soft drink and 100% fruit juice consumption with all-cause mortality, cardiovascular diseases mortality, and cancer mortality: A systematic review and dose-response meta-analysis of prospective cohort studies - Bei Pan; Long Ge; Honghao Lai; Qi Wang; Qi Wang; Qian Zhang; Min Yin; Sheng Li; Jinhui Tian; Kehu Yang; Jiancheng Wang (Critical Reviews in Food Science and Nutrition, 2022)

Transport Patterns and Potential Sources of Atmospheric Pollution during the XXIV Olympic Winter Games Period - Yuting Zhang; Xiaole Pan; Yu Tian; Hang Liu; Xueshun Chen; Baozhu Ge; Zhe Wang; Xiao Tang; Shandong Lei; Weijie Yao; Yuanzhe Ren; Yongli Tian; et al. (Advances in Atmospheric Sciences, 2022)
The attainment of suitable ambient air quality standards is a matter of great concern for successfully hosting the XXIV Olympic Winter Games (OWG). Transport patterns and potential sources of pollutants in Zhangjiakou (ZJK) were investigated using pollutant monitoring datasets and a dispersion model. The PM 2.5 concentration during February in ZJK has increased slightly (28%) from 2018 to 2021, mostly owing to the shift of main potential source regions of west-central Inner Mongolia and Mongolian areas (2015–18) to the North China Plain and northern Shanxi Province (NCPS) after 2018. Using CO as an indicator, the relative contributions of the different regions to the receptor site (ZJK) were evaluated based on the source-receptor-relationship method (SRR) and an emission inventory. We found that the relative contribution of pollutants from NCPS increased from 33% to 68% during 2019–21. Central Inner Mongolia (CIM) also has an important impact on ZJK under unfavorable weather conditions. This study demonstrated that the effect of pollution control measures in the NCPS and CIM should be strengthened to ensure that the air quality meets the standard during the XXIV OWG.

Spatial variation in bacterial community and dissolved organic matter composition in groundwater near a eutrophic lake - Ning Ma; Li Gao; Yan Zhang; Zhengkui Ge; En Hu; Baozhu Pan; Jian Wang; Ming Li (Aquatic Ecology, 2022)

Dynamic changes of reactive oxygen species in paddy overlying water: mechanisms and implications - Shaochong Liu; Mengxi Tan; Danyu Huang; Dixiang Wang; Mengyuan Geng; Jialin Wen; Changyin Zhu; Liqiang Ge; Ning Chen; Yan Gao; Jiangye Li; Jianbin Pan; et al. (Journal of Soils and Sediments, 2022)

Modeling wide-area tropospheric delay corrections for fast PPP ambiguity resolution - Bobin Cui; Jungang Wang; Pan Li; Maorong Ge; Harald Schuh (GPS Solutions, 2022)
The performance of precise point positioning (PPP) has been significantly improved thanks to the continuous improvements in satellite orbit, clock, and ambiguity resolution (AR) technologies, but the convergence speed remains a limiting factor in real-time PPP applications. To improve the PPP precision and convergence time, tropospheric delays from a regional network can be modeled to provide precise correction for users. We focus on the precise modeling of zenith wet delay (ZWD) over a wide area with large altitude variations for improving PPP-AR. By exploiting the water vapor exponential vertical decrease, we develop a modified optimal fitting coefficients (MOFC) model based on the traditional optimal fitting coefficients (OFC) model. The proposed MOFC model provides a precision better than 1.5 cm under sparse inter-station distances over the Europe region, with a significant improvement of 70% for high-altitude stations compared to the OFC model. The MOFC model with different densities of reference stations is further evaluated in GPS and Galileo kinematic PPP-AR solutions. Compared to the PPP-AR solutions without tropospheric delay augmentation, the positioning precision of those with 100-km inter-station spacing MOFC and OFC is improved by 25.7% and 17.8%, respectively, and the corresponding time to first fix (TTFF) is improved by 36.9% and 33.0% in the high-altitude areas. On the other hand, the OFC model only slightly improves the TTFF and positioning accuracy when using the 200 km inter-station spacing modeling and even degrades the positioning for high-altitude stations, whereas using the MOFC model, the PPP-AR solutions always improve. Moreover, the positioning precision improvement of MOFC compared with OFC is about 22.1%, 21.7%, and 25.7% for the Galileo-only, GPS-only, and GPS + Galileo PPP-AR solutions, respectively.

Changes in the waterbird community of the Yangtze River in the Three Gorges Reservoir Region, China, 2003–2013 - Xiuming Li; Wenfa Xiao; Ge Sun; Tian Ma; Fuguo Liu; Xiaoyun Liu; Hualong Su; Kaijun Pan; Ruimei Cheng; Fawen Qian (Biologia, 2022)

Identification and analysis of oil candidate genes reveals the molecular basis of cottonseed oil accumulation in Gossypium hirsutum L. - Zhibin Zhang; Juwu Gong; Zhen Zhang; Wankui Gong; Junwen Li; Yuzhen Shi; Aiying Liu; Qun Ge; Jingtao Pan; Senmiao Fan; Xiaoying Deng; Shaoqi Li; et al. (Theoretical and Applied Genetics, 2022)

Identification of key gene networks controlling vernalization development characteristics of Isatis indigotica by full-length transcriptomes and gene expression profiles - Pan Wang; Dong Liu; Fu-Hong Yang; Hui Ge; Xin Zhao; Hong-Gang Chen; Tao Du (Physiology and Molecular Biology of Plants, 2021)
Isatis indigotica Fort . , as a common Chinese medicinal raw material, will lose its medicinal value if it blooms early, so it is highly valuable to clarify the induction mechanism of the vernalization of I. indigotica at low temperature. In this study, the concentrations of soluble sugar, proline, glutathione and zeatin in two germplasms of I. indigotica with different degrees of low temperature tolerance (Y1 and Y2) were determined at 10 days, 20 days and 30 days of low-temperature treatment, and the full-length transcriptome of 24 samples was sequenced by Nanopore sequencing with Oxford Nanopore Technologies (ONT). After that, the data of transcripts involved in the vernalization of I. indigotica at low temperature were obtained, and these transcripts were identified using weighted gene co-expression network analysis (WGCNA). The results revealed the massive accumulation of soluble sugar and proline in Y1 and Y2 after low temperature induction. A total of 18,385 new transcripts, 6168 transcription factors and 470 lncRNAs were obtained. Differential expression analysis showed that gibberellin, flavonoids, fatty acids and some processes related to low temperature response were significantly enriched. Eight key transcripts were identified by WGCNA, among which ONT.14640.1, ONT.9119.1, ONT.13080.2 and ONT.16007.1 encodes a flavonoid transporter, 9-cis-epoxycarotenoid dioxygenase 3 (NCED3), growth factor gene and L-aspartate oxidase in plants, respectively . It indicated that secondary metabolites such as hormones and flavonoids play an important role in the vernalization of I. indigotica . qRT-PCR proved the reliability of transcriptome results. These results provide important insights on the low-temperature vernalization of I. indigotica , and provide a research basis for analyzing the vernalization mechanism of I. indigotica .

The impacts of different anticoagulants and long-term frozen storage on multiple metal concentrations in peripheral blood: a comparative study - Yu Bao; Xiaoting Ge; Longman Li; Junxiu He; Sifang Huang; Xiaoyu Luo; Xing Chen; Pan Chen; Xiaobo Yang (BioMetals, 2021)

Retraction Note to: CiRS-126 inhibits proliferation of ovarian granulosa cells through targeting the miR-21-PDCD4-ROS axis in a polycystic ovarian syndrome model - Jiafeng Lu; Ying Xue; Yuhang Wang; Yang Ding; Qinyan Zou; Min Pan; Longwei Qiao; Chunhua Zhang; Qinyu Ge; Ting Wang; Hong Li (Cell and Tissue Research, 2021)

A semi-supervised learning method for hyperspectral imagery based on self-training and local-based affinity propagation - Haimiao Ge; Haizhu Pan; Liguo Wang; Cheng Li; Yanzhong Liu; Wenlong Zhu; Yanping Teng (International Journal of Remote Sensing, 2021)

Development of nuclear and chloroplast polymorphic microsatellites for Crossostephium chinense (Asteraceae) - Luxian Liu; Shook Ling Low; Shota Sakaguchi; Yu Feng; Binjie Ge; Kamil Konowalik; Pan Li (Molecular Biology Reports, 2021)

Transcriptome analysis reveals hub genes in the hepatopancreas of Exopalaemon carinicauda in response to hypoxia and reoxygenation - Wenjun Shi; Pan Wang; Runhao Hu; Xihe Wan; Hui Shen; Hui Li; Libao Wang; Yi Qiao; Ge Jiang; Jie Cheng; Zeyu Yang (Aquaculture International, 2021)

Calibrating receiver-type-dependent wide-lane uncalibrated phase delay biases for PPP integer ambiguity resolution - Bobin Cui; Pan Li; Jungang Wang; Maorong Ge; Harald Schuh (Journal of Geodesy, 2021)
Wide-lane (WL) uncalibrated phase delay (UPD) is usually derived from Melbourne–Wübbena (MW) linear combination and is a prerequisite in Global Navigation Satellite Systems (GNSS) precise point positioning (PPP) ambiguity resolution (AR). MW is a linear combination of pseudorange and phase, and the accuracy is limited by the larger pseudorange noise which is about one hundred times of the carrier phase noise. However, there exist inconsistent pseudorange biases which may have detrimental effect on the WL UPD estimation, and further degrade user-side ambiguity fixing. Currently, only the large part of pseudorange biases, e.g., the differential code bias (DCB), are available and corrected in PPP-AR, while the receiver-type-dependent biases have not yet been considered. Ignoring such kind of bias, which could be up to 20 cm, will cause the ambiguity fixing failure, or even worse, the incorrect ambiguity fixing. In this study, we demonstrate the receiver-type-dependent WL UPD biases and investigate their temporal and spatial stability, and further propose the method to precisely estimate these biases and apply the corrections to improve the user-side PPP-AR. Using a large data set of 1560 GNSS stations during a 30-day period, we demonstrate that the WL UPD deviations among different types of receivers can reach ± 0.3 cycles. It is also shown that such kind of deviations can be calibrated with a precision of about 0.03 cycles for all Global Positioning System (GPS) satellites. On the user side, ignoring the receiver-dependent UPD deviation can cause significant positioning error up to 10 cm. By correcting the deviations, the positioning performance can be improved by up to 50%, and the fixing rate can also be improved by 10%. This study demonstrates that for the precise and reliable PPP-AR, the receiver-dependent UPD deviations cannot be ignored and have to be handled.

Identification and functional characterization of a new flavonoid synthase gene MdFLS1 from apple - Pan Li; Kang Lei; Lin Liu; Guizhi Zhang; Hongjuan Ge; Chengchao Zheng; Huairui Shu; Shizhong Zhang; Lusha Ji (Planta, 2021)

Molecular cloning and functional characterization of the hypoxia-inducible factor-1α in bighead carp (Aristichthys nobilis) - Yan Lin; Ling-Hong Miao; Bo Liu; Bing-Wen Xi; Liang-Kun Pan; Xian-Ping Ge (Fish Physiology and Biochemistry, 2021)

Risk evaluation of dam-break environmental impacts based on the set pair analysis and cloud model - Wei Ge; Zongkun Li; Wei Li; Meimei Wu; Juanjuan Li; Yipeng Pan (Natural Hazards, 2020)

Effects of Al stress on the growth and nitrogen uptake of maize varieties with different Al tolerance as related with Al chemical forms on root surfaces - Xiao-ying Pan; Ge Dong; Xian He; Ru-hai Wang; Ren-kou Xu; Ting-ting Mu (Journal of Soils and Sediments, 2020)

A combination of linkage mapping and GWAS brings new elements on the genetic basis of yield-related traits in maize across multiple environments - Xiaoxiang Zhang; Zhongrong Guan; Zhaoling Li; Peng Liu; Langlang Ma; Yinchao Zhang; Lang Pan; Shijiang He; Yanling Zhang; Peng Li; Fei Ge; Chaoying Zou; et al. (Theoretical and Applied Genetics, 2020)

Seasonal temperature response over the Indochina Peninsula to a worst-case high-emission forcing: a study with the regionally coupled model ROM - Shoupeng Zhu; Fei Ge; Frank Sielmann; Mengting Pan; Klaus Fraedrich; Armelle Reca C. Remedio; Dmitry V. Sein; Daniela Jacob; Hao Wang; Xiefei Zhi (Theoretical and Applied Climatology, 2020)

Toxic effects of heavy metals on the freshwater benthic organisms in sediments and research on quality guidelines in Poyang Lake, China - Ping Zhang; Xuemei Pan; Qinyuan Wang; Gang Ge; Yun Huang (Journal of Soils and Sediments, 2020)

Comparison of proteome alterations during aging in the temporal lobe of humans and rhesus macaques - Xia Wang; Kang Chen; Meng Pan; Wei Ge; Zhanlong He (Experimental Brain Research, 2020)

Examining two sets of introgression lines across multiple environments reveals background-independent and stably expressed quantitative trait loci of fiber quality in cotton - Yuzhen Shi; Aiying Liu; Junwen Li; Jinfa Zhang; Shaoqi Li; Jinfeng Zhang; Liujun Ma; Rui He; Weiwu Song; Lixue Guo; Quanwei Lu; Xianghui Xiang; et al. (Theoretical and Applied Genetics, 2020)
Key message Background-independent (BI) and stably expressed (SE) quantitative trait loci (QTLs) were identified using two sets of introgression lines across multiple environments. Genetic background more greatly affected fiber quality traits than environmental factors. Sixty-one SE-QTLs, including two BI-QTLs, were novel and 48 SE-QTLs, including seven BI-QTLs, were previously reported. Abstract Cotton fiber quality traits are controlled by QTLs and are susceptible to environmental influence. Fiber quality improvement is an essential goal in cotton breeding but is hindered by limited knowledge of the genetic basis of fiber quality traits. In this study, two sets of introgression lines of Gossypium hirsutum × G. barbadense were used to dissect the QTL stability of three fiber quality traits (fiber length, strength and micronaire) across environments using 551 simple sequence repeat markers selected from our high-density genetic map. A total of 76 and 120 QTLs were detected in the CCRI36 and CCRI45 backgrounds, respectively. Nine BI-QTLs were found, and 78 (41.71%) of the detected QTLs were reported previously. Thirty-nine and 79 QTLs were SE-QTLs in at least two environments in the CCRI36 and CCRI45 backgrounds, respectively. Forty-eight SE-QTLs, including seven BI-QTLs, were confirmed in previous reports, and 61 SE-QTLs, including two BI-QTLs, were considered novel. These results indicate that genetic background more strongly impacts on fiber quality traits than environmental factors. Twenty-three clusters with BI- and/or SE-QTLs were identified, 19 of which harbored favorable alleles from G. barbadense for two or three fiber quality traits. This study is the first report using two sets of introgression lines to identify fiber quality QTLs across environments in cotton, providing insights into the effect of genetic backgrounds and environments on the QTL expression of fiber quality and important information for the genetic basis underlying fiber quality traits toward QTL cloning and molecular breeding.

GPS + Galileo + BeiDou precise point positioning with triple-frequency ambiguity resolution - Pan Li; Xinyuan Jiang; Xiaohong Zhang; Maorong Ge; Harald Schuh (GPS Solutions, 2020)
Along with the rapid development of GNSS, not only BeiDou, but also Galileo, and the newly launched GPS satellites can provide signals on three frequencies at present. To fully take advantage of the multi-frequency multi-system GNSS observations on precise point positioning (PPP) technology, this study aims to implement the triple-frequency ambiguity resolution (AR) for GPS, Galileo, and BeiDou-2 combined PPP using the raw observation model. The processing of inter-frequency clock bias (IFCB) estimation and correction in the context of triple-frequency PPP AR has been addressed, with which the triple-frequency uncalibrated phase delay (UPD) estimation is realized for real GPS observations for the first time. In addition, the GPS extra-wide-line UPD quality is significantly improved with the IFCB correction. Because of not being contaminated by the IFCB, the raw UPD estimation method is directly employed for Galileo which currently has 24 satellites in operation. An interesting phenomenon is found that all Galileo satellites except E24 have a zero extra-wide-lane UPD value. With the multi-GNSS observations provided by MGEX covering 15 days, the positioning solutions of GPS + Galileo + BeiDou triple-frequency PPP AR have been conducted and analyzed. The triple-frequency kinematic GNSS PPP AR can achieve an averaged 3D positioning error of 2.2 cm, and an averaged convergence time of 10.8 min. The average convergence time can be reduced by triple-frequency GNSS PPP AR by 15.6% compared with dual-frequency GNSS PPP AR, respectively. However, the additional third frequency has only a marginal contribution to positioning accuracy after convergence.

RETRACTED ARTICLE: CiRS-126 inhibits proliferation of ovarian granulosa cells through targeting the miR-21-PDCD4-ROS axis in a polycystic ovarian syndrome model - Jiafeng Lu; Ying Xue; Yuhang Wang; Yang Ding; Qinyan Zou; Min Pan; Longwei Qiao; Chunhua Zhang; Qinyu Ge; Ting Wang; Hong Li (Cell and Tissue Research, 2020)

Establishment of a maize callus regeneration system from haploid shoot tips - Yun Long; Yun Yang; Fei Ge; Guangtang Pan; Yaou Shen (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)

The spatial distribution of the normal reference values of the activated partial thromboplastin time based on ArcGIS and GeoDA - Shaofang Yang; Miao Ge; Xiaoping Li; Chiqin Pan (International Journal of Biometeorology, 2020)

Combination of multi-locus genome-wide association study and QTL mapping reveals genetic basis of tassel architecture in maize - Yanli Wang; Jie Chen; Zhongrong Guan; Xiaoxiang Zhang; Yinchao Zhang; Langlang Ma; Yiming Yao; Huanwei Peng; Qian Zhang; Biao Zhang; Peng Liu; Chaoying Zou; et al. (Molecular Genetics and Genomics, 2019)

Dissecting the genetic basis of fiber quality and yield traits in interspecific backcross populations of Gossypium hirsutum × Gossypium barbadense - Yuzhen Shi; Aiying Liu; Junwen Li; Jinfa Zhang; Baocai Zhang; Qun Ge; Muhammad Jamshed; Quanwei Lu; Shaoqi Li; Xianghui Xiang; Juwu Gong; Wankui Gong; et al. (Molecular Genetics and Genomics, 2019)

Rapid adaptation of Brachionus angularis (Rotifera) to invasion by Brachionus calyciflorus - Yi-Long Xi; Ke-Qiang Huang; Ling Pan; Han Zhu; Ya-Li Ge; Xin-Li Wen; Xian-Ling Xiang (Hydrobiologia, 2019)

Regulation of bile acid metabolism-related signaling pathways by gut microbiota in diseases - Er-teng Jia; Zhi-yu Liu; Min Pan; Jia-feng Lu; Qin-yu Ge (Journal of Zhejiang University-SCIENCE B, 2019)

Multipath extraction and mitigation for high-rate multi-GNSS precise point positioning - Kai Zheng; Xiaohong Zhang; Pan Li; Xingxing Li; Maorong Ge; Fei Guo; Jizhang Sang; Harald Schuh (Journal of Geodesy, 2019)

Kalman-filter-based undifferenced cycle slip estimation in real-time precise point positioning - Pan Li; Xinyuan Jiang; Xiaohong Zhang; Maorong Ge; Harald Schuh (GPS Solutions, 2019)

Nitrous oxide emission rate in response to plant, soil and microbial properties in marshes impacted by alien Spartina alterniflora - Chongbang Zhang; Wenli Liu; Ming Guan; Jiang Wang; Xiaocui Pan; Ying Ge; Jie Chang (Biologia, 2019)

Potential impacts of climate change on vegetation dynamics and ecosystem function in a mountain watershed on the Qinghai-Tibet Plateau - Decheng Zhou; Lu Hao; John B. Kim; Peilong Liu; Cen Pan; Yongqiang Liu; Ge Sun (Climatic Change, 2019)

In Vitro Evaluation of Probiotic Potential of Lactic Acid Bacteria Isolated from Yunnan De’ang Pickled Tea - Zhenhui Cao; Hongbin Pan; Shijun Li; Chongying Shi; Sifan Wang; Fuyi Wang; Pengfei Ye; Junjing Jia; Changrong Ge; Qiuye Lin; Zhiyong Zhao (Probiotics and Antimicrobial Proteins, 2019)

Three-frequency BDS precise point positioning ambiguity resolution based on raw observables - Pan Li; Xiaohong Zhang; Maorong Ge; Harald Schuh (Journal of Geodesy, 2018)

White matter integrity correlates with residual consciousness in patients with severe brain injury - Lubin Wang; Yi Yang; Shanshan Chen; Mingmei Ge; Jianghong He; Zheng Yang; Pan Lin; Xinhuai Wu (Brain Imaging and Behavior, 2018)

Novel characterization method of impedance cardiography signals using time-frequency distributions - Jesús Escrivá Muñoz; Y. Pan; S. Ge; E. W. Jensen; M. Vallverdú (Medical & Biological Engineering & Computing, 2018)

TMEM88 mediates inflammatory cytokines secretion by regulating JNK/P38 and canonical Wnt/β-catenin signaling pathway in LX-2 cells - Tao Xu; Lin-xin Pan; Yun-xuan Ge; Peng Li; Xiao-ming Meng; Cheng Huang; Jun Li (Inflammopharmacology, 2018)

OsERF101, an ERF family transcription factor, regulates drought stress response in reproductive tissues - Yue Jin; Weiyang Pan; Xiufang Zheng; Xuan Cheng; Mengmeng Liu; Hong Ma; Xiaochun Ge (Plant Molecular Biology, 2018)

Correction to: p-Coumaric acid can alter the composition of cucumber rhizosphere microbial communities and induce negative plant-microbial interactions - Xingang Zhou; Jianhui Zhang; Dandan Pan; Xin Ge; Xue Jin; Shaocan Chen; Fengzhi Wu (Biology and Fertility of Soils, 2018)

Homoeolog Expression Is Modulated Differently by Different Subgenomes in Brassica napus Hybrids and Allotetraploids - Dawei Zhang; Qi Pan; Chen Tan; Lili Liu; Xianhong Ge; Zaiyun Li; Mingli Yan (Plant Molecular Biology Reporter, 2018)

Effect of nitrite exposure on oxygen-carrying capacity and gene expression of NF-κB/HIF-1α pathway in gill of bighead carp (Aristichthys nobilis) - Yan Lin; Ling-Hong Miao; Wu-Xiao Zhang; Wen-Jing Pan; Hua-Liang Liang; Xian-Ping Ge; Yan-Shun Xu; Bo Liu; Ming-Chun Ren; Qun-Lan Zhou; Si-Lei Xia (Aquaculture International, 2018)

Evaluation of vulnerable PM2.5-exposure individuals: a repeated-measure study in an elderly population - Haiyan Chu; Junyi Xin; Qi Yuan; Xu Zhang; Wang Pan; Xinying Zeng; Yaoyao Chen; Gaoxiang Ma; Yuqiu Ge; Mulong Du; Na Tong; Xiaobo Li; et al. (Environmental Science and Pollution Research, 2018)

p-Coumaric can alter the composition of cucumber rhizosphere microbial communities and induce negative plant-microbial interactions - Xingang Zhou; Jianhui Zhang; Dandan Pan; Xin Ge; Xue Jin; Shaocan Chen; Fengzhi Wu (Biology and Fertility of Soils, 2018)

Simultaneous estimation of GLONASS pseudorange inter-frequency biases in precise point positioning using undifferenced and uncombined observations - Feng Zhou; Danan Dong; Maorong Ge; Pan Li; Jens Wickert; Harald Schuh (GPS Solutions, 2018)

Analysis on biomass and productivity of epilithic algae and their relations to environmental factors in the Gufu River basin, Three Gorges Reservoir area, China - Jiwen Ge; Shuyuan Wu; Dado Touré; Lamei Cheng; Wenjie Miao; Huafen Cao; Xiaoying Pan; Jianfeng Li; Minmin Yao; Liang Feng (Environmental Science and Pollution Research, 2017)

Study of aircraft icing warning algorithm based on millimeter wave radar - Jinhu Wang; Junxiang Ge; Qilin Zhang; Pan Fan; Ming Wei; Xiangchao Li (Journal of Meteorological Research, 2017)

Bioinformatic prediction and analysis of glucolipid metabolic regulation by miR-34a in Megalobrama amblycephala - Ling-Hong Miao; Wen-Jing Pan; Yan Lin; Xian-Ping Ge; Bo Liu; Ming-Chun Ren; Qun-Lan Zhou (Genes & Genomics, 2017)

Deletion of mammalian sterile 20-like kinase 1 attenuates neuronal loss and improves locomotor function in a mouse model of spinal cord trauma - Pan-feng Wang; Da-yuan Xu; Yuntong Zhang; Xiao-bin Liu; Yan Xia; Pan-yu Zhou; Qing-ge Fu; Shuo-gui Xu (Molecular and Cellular Biochemistry, 2017)

Near-Infrared Spectroscopy Assay of Key Quality-Indicative Ingredients of Tongkang Tablets - Wenjie Pan; Jinfang Ma; Xue Xiao; Zhengwei Huang; Huanbin Zhou; Fahuan Ge; Xin Pan (AAPS PharmSciTech, 2017)

Rapid identification of QTLs underlying resistance to Cucumber mosaic virus in pepper (Capsicum frutescens) - Guangjun Guo; Shubin Wang; Jinbing Liu; Baogui Pan; Weiping Diao; Wei Ge; Changzhou Gao; John C. Snyder (Theoretical and Applied Genetics, 2017)

A strategy for introducing an endangered plant Mosla hangchowensis to urban area based on nitrogen preference - Mei-Ying Fan; Kai-Xuan Pan; Wen-Juan Han; Yi-Jun Lu; Qi Shen; Meng Wang; Yuan Ren; Ze-Long Qu; Jie Chang; Ying Ge (Acta Physiologiae Plantarum, 2016)

Expression of inflammation-related genes in the lung of BALB/c mice response to H7N9 influenza A virus with different pathogenicity - Meng Yu; Qingnan Wang; Wenbao Qi; Kaizhao Zhang; Jianxin Liu; Pan Tao; Shikun Ge; Ming Liao; Zhangyong Ning (Medical Microbiology and Immunology, 2016)

Highly selective and efficient biotransformation of linarin to produce tilianin by naringinase - Pan Cui; Tong-Yi Dou; Shi-Yang Li; Jun-Xia Lu; Li-Wei Zou; Ping Wang; Yan-Ping Sun; Da-Cheng Hao; Guang-Bo Ge (Biotechnology Letters, 2016)

Expression Profile and Tissue-Specific Distribution of the Receptor-Interacting Protein 3 in BALB/c Mice - Qingnan Wang; Meng Yu; Kaizhao Zhang; Jianxin Liu; Pan Tao; Shikun Ge; Zhangyong Ning (Biochemical Genetics, 2016)

Estimates of long-term water total phosphorus (TP) concentrations in three large shallow lakes in the Yangtze River basin, China - Pan Wu; Boqiang Qin; Ge Yu (Environmental Science and Pollution Research, 2016)

The activity parameters, cDNA cloning and mRNA expression of lysozyme in Cyclina sinensis (Bivalvia, Veneridae) responding to the pathogenic bacterium Vibrio anguillarum - Pan Baoping; Wei Xing; Gao Jing; Luo Kaiya; Ge Duanyan (Molluscan Research, 2016)

Trends in the prevalence of heart diseases over a ten-year period from single-center observations based on a large echocardiographic database - Hao Lu; Wen-zhi Pan; Quan Wan; Lei-lei Cheng; Xian-hong Shu; Cui-zhen Pan; Ju-ying Qian; Jun-bo Ge (Journal of Zhejiang University-SCIENCE B, 2016)

Passive-source multitaper-spectral method based low-frequency data reconstruction for active seismic sources - Pan Zhang; Li-Guo Han; Yan Zhou; Zhuo Xu; Qi-Xin Ge (Applied Geophysics, 2015)

A fast-convergence POCS seismic denoising and reconstruction method - Zi-Jian Ge; Jing-Ye Li; Shu-Lin Pan; Xiao-Hong Chen (Applied Geophysics, 2015)

Reconnaissance report on buildings damaged during the Lushan earthquake, April 20, 2013 - Feng Xiong; Lingzhi Xie; Qi Ge; Yuxin Pan; Moe Cheung (Natural Hazards, 2015)

Role of Interleukin-22 in liver diseases - Chun-xiao Pan; Jie Tang; Xiao-yu Wang; Fan-rong Wu; Jin-fang Ge; Fei-hu Chen (Inflammation Research, 2014)

Bioinformatic identification and validation of conservative microRNAs in Ictalurus punctatus - Zhiqiang Xu; Qin Qin; Jiachun Ge; Jianlin Pan; Xiaofeng Xu (Molecular Biology Reports, 2012)

Isolation of yellow catfish β-actin promoter and generation of transgenic yellow catfish expressing enhanced yellow fluorescent protein - Jiachun Ge; Zhangji Dong; Jingyun Li; Zhiqiang Xu; Wei Song; Jie Bao; Dong Liang; Junbo Li; Kui Li; Wenshuang Jia; Muzi Zhao; Yongxiang Cai; et al. (Transgenic Research, 2012)

Exercise preconditioning provides early cardioprotection against exhaustive exercise in rats: potential involvement of protein kinase C delta translocation - Yu-Jun Shen; Shan-Shan Pan; Jun Ge; Zhe Hao (Molecular and Cellular Biochemistry, 2012)

Century-Scale Responses of Ecosystem Carbon Storage and Flux to Multiple Environmental Changes in the Southern United States - Hanqin Tian; Guangsheng Chen; Chi Zhang; Mingliang Liu; Ge Sun; Arthur Chappelka; Wei Ren; Xiaofeng Xu; Chaoqun Lu; Shufen Pan; Hua Chen; Dafeng Hui; et al. (Ecosystems, 2012)

Analysis on the interaction between IL-1F7 gene and environmental factors on patients with ankylosing spondylitis: a case-only study - Rui Ge; Faming Pan; Fangfang Liao; Guo Xia; Yang Mei; Beibei Shen; Tianchen Zhang; Jing Gao; Li Zhang; Zhenhua Duan; Shengqian Xu; Jianhua Xu (Molecular Biology Reports, 2011)

Expression and identification of a thermostable malate dehydrogenase from multicellular prokaryote Streptomyces avermitilis MA-4680 - Zong-Da Wang; Bao-Juan Wang; Ya-Dong Ge; Wei Pan; Jie Wang; Lei Xu; Ai-Min Liu; Guo-Ping Zhu (Molecular Biology Reports, 2011)

Impact of female cigarette smoking on circulating B cells in vivo: the suppressed ICOSLG, TCF3, and VCAM1 gene functional network may inhibit normal cell function - Feng Pan; Tie-Lin Yang; Xiang-Ding Chen; Yuan Chen; Ge Gao; Yao-Zhong Liu; Yu-Fang Pei; Bao-Yong Sha; Yan Jiang; Chao Xu; Robert R. Recker; Hong-Wen Deng (Immunogenetics, 2010)

Dissipation and residue of famoxadone in grape and soil - Jing Ge; Dongmei Qin; Yuzhen Zhao; Canping Pan; Shuren Jiang; Fengmao Liu (Environmental Monitoring and Assessment, 2010)

No significant association between Fc receptor-like 3 gene polymorphisms and human leukocyte antigen-B27 positive ankylosing spondylitis in Han Chinese population - Guo Xia; Faming Pan; Fangfang Liao; Xiaowu Tang; Rui Ge; Yang Mei; Heping Pan; Shengqian Xu; Jianhua Xu (Molecular Biology Reports, 2010)

Magnetic cell sorting and flow cytometry sorting methods for the isolation and function analysis of mouse CD4+ CD25+ Treg cells - Hang Yan; Chen-guang Ding; Pu-xun Tian; Guan-qun Ge; Zhan-kui Jin; Li-ning Jia; Xiao-ming Ding; Xiao-ming Pan; Wu-jun Xue (Journal of Zhejiang University-SCIENCE B, 2009)

Risk to humans of consuming metals in anchovy (Coilia sp.) from the Yangtze River Delta - Fengyan Liu; Jiachun Ge; Xin Hu; Teng Fei; Yuehua Li; Yuan Jiang; Zhiqiang Xu; Shuyan Ding; John P. Giesy; Jianlin Pan (Environmental Geochemistry and Health, 2009)

Inactivation of Dipeptidyl Peptidase IV Attenuates the Virulence of Streptococcus suis Serotype 2 that Causes Streptococcal Toxic Shock Syndrome - Junchao Ge; Youjun Feng; Hongfeng Ji; Huimin Zhang; Feng Zheng; Changjun Wang; Zhimin Yin; Xiuzhen Pan; Jiaqi Tang (Current Microbiology, 2009)

The contribution of proline residues to protein stability is associated with isomerization equilibrium in both unfolded and folded states - Meng Ge; Xian-Ming Pan (Extremophiles, 2009)

Refolding of the hyperthermophilic protein Ssh10b involves a kinetic dimeric intermediate - Meng Ge; Yong-Jin Mao; Xian-Ming Pan (Extremophiles, 2009)

The involvement of sortase A in high virulence of STSS-causing Streptococcus suis serotype 2 - Changjun Wang; Ming Li; Youjun Feng; Feng Zheng; Yaqing Dong; Xiuzhen Pan; Gong Cheng; Ruiping Dong; Dan Hu; Xiaodan Feng; Junchao Ge; Di Liu; et al. (Archives of Microbiology, 2009)

New Fluorescent Labels: 4- and 7-Chlorofluorescein - Feng-Yan Ge; Xi-Long Yan; Fan-Yong Yan; Hui-Ying Pan; Li-Gong Chen (Journal of Fluorescence, 2005)

Reconfirmation of antimicrobial activity in the coelomic fluid of the earthwormEisenia fetida andrei by colorimetric assay - Weidong Pan; Xianghui Liu; Feng Ge; Tao Zheng (Journal of Biosciences, 2003)